Room-temperature biosynthesis of ferroelectric barium titanate nanoparticles - Bansal, Vipul; Poddar, Pankaj; Ahmad, Absar; Sastry, Murali (Journal of the American Chemical Society, 2006)
The syntheses of inorganic materials by biological systems is characterized by processes that occur close to ambient temperatures, pressures, and neutral pH, as is exemplified by biosilicification and biomineralization processes in nature. Conversely, laboratory-based syntheses of oxide materials often require extremes of temperature and pressure. We have shown here the extracellular, room-temperature biosynthesis of 4-5 nm ternary oxide nanoparticles such as barium titanate (BT) using a fungus-mediated approach. The tetragonality as well as a lowered Curie transition temperature in sub-10 nm particles was established, and the ferroelectricity in these particles was shown using Kelvin probe microscopy.

Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Imaging the interaction between dengue 2 virus and human blood platelets using atomic force and electron microscopy - Ghosh, Kanjaksha; Gangodkar, Shobha; Jain, Preksha; Shetty, Shrimati; Ramjee, Sandhya; Poddar, Pankaj; Basu, Atanu (Journal of Electron Microscopy, 2008)
Thrombocytopenia is frequently associated with dengue virus infection. Host factors such as anti-platelet immunopathogenic processes have been implicated in the origin of dengue-associated thrombocytopenia but the role of dengue virus in directly interacting with platelets and altering their hemostatic property remains incompletely understood. In the present study, we examined the effect of dengue 2 virus on the morphology and physiological activation profile of normal human platelets using atomic force microscopy, electron microscopy and flowcytometry. Platelets obtained from healthy donors were exposed to a cell culture-adapted 10(4) LD(50) dengue 2 virus isolate in vitro and the subsequent effect on morphology and activation biology studied. Our results show that dengue 2 virus exposure at doses comparable to natural viremic states in human infections can activate platelets with an increase in P-selectin expression and fibrinogen-binding property. Atomic force, scanning and transmission electron microscopy also showed typical activation-related morphological changes such as altered platelet membrane architecture, degranulation, presence of filopodia and dilatation of the open canalicular system in the dengue 2 virus-exposed platelets but not in the controls. Importantly, Japanese encephalitis virus exposure at the same dose did not activate platelets or show any morphological changes. Our findings suggest that dengue 2 virus may directly interact with and activate platelets - an event that might be important in the origin of dengue-associated thrombocytopenia. Detailed molecular characterization of this effect might provide key knowledge toward better prophylaxis of the hemostatic complications of dengue disease.
Keywords: AFM; dengue virus; Electron microscopy; platelet

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Transverse susceptibility study of the effect of varying dipolar interactions on anisotropy peaks in a three-dimensional assembly of soft ferrite nanoparticles - Poddar, Pankaj; Morales, Marienette B.; Frey, Natalie A.; Morrison, Shannon A.; Carpenter, Everett E.; Srikanth, Hariharan (Journal of Applied Physics, 2008)
Collective magnetization dynamics in nanoparticle assemblies is of current interest as it forms the basis of high density storage media. It is important to understand how interparticle interactions in a three-dimensional (3D) arrangement of superparamagnetic nanoparticles would affect the overall effective magnetic anisotropy of the system. We have studied the influence of varying strengths of dipolar interaction on the static and dynamic magnetic properties of surfactant-coated monodispersed manganese zinc ferrite nanoparticles using reversible transverse susceptibility. We track the evolution of the anisotropy peaks with varying magnetic field, temperature, and interaction strength. The blocking temperature shows an increase from 28 to 32 K and the coercive field (at 10 K) shows an increase from 144 to 192 Oe as the system changes from the case of weakly interacting to strongly interacting 3D assembly of the particles. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.2977592]

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Human blood vessel-derived endothelial progenitors for endothelialization of small diameter vascular prosthesis - Ranjan, Amaresh K.; Kumar, Umesh; Hardikar, Ashutosh A.; Poddar, Pankaj; Nair, Prabha D.; Hardikar, Anandwardhan A. (Plos One, 2009)
Background: Coronary bypass graft failure as a result of acute thrombosis and intimal hyperplasia has been the major challenge in surgical procedures involving small-diameter vascular prosthesis. Coating synthetic grafts with patients' own endothelial cells has been suggested to improve the patency rate and overall success of bypass surgeries. Methodology/Principal Findings: We isolated endothelial progenitor cells (EPCs) from leftover pieces of human saphenous vein/mammary artery. We demonstrate that EPCs can be expanded to generate millions of cells under low-density culture conditions. Exposure to high-density conditions induces differentiation to endothelial cell phenotype. EPC-derived endothelial cells show expression of CD144(high), CD31, and vWF. We then assessed the ability of differentiated endothelial cells to adhere and grow on small diameter expanded polytetrafluoroethylene (ePTFE) tubings. Since ePTFE tubings are highly hydrophobic, we optimized protocols to introduce hydrophilic groups on luminal surface of ePTFE tubings. We demonstrate here a stepwise protocol that involves introduction of hydrophilic moieties and coating with defined ECM components that support adhesion of endothelial cells, but not of blood platelets. Conclusion/Significance: Our data confirms that endothelial progenitors obtained from adult human blood vessels can be expanded in vitro under xenoprotein-free conditions, for potential use in endothelialization of small diameter ePTFE grafts. These endothelialized grafts may represent a promising treatment strategy for improving the clinical outcome of small-caliber vascular grafts in cardiac bypass surgeries.

In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity

Preparation of nearly monodisperse nickel nanoparticles by a facile solution based methodology and their ordered assemblies - Sidhaye, Deepti S.; Bala, Tanushree; Srinath, S.; Srikanth, H.; Poddar, Pankaj; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2009)
Nickel nanoparticles have been synthesized by a simple wet chemical reduction technique in the presence of a surfactant sodium dodecyl sulfate (SDS) and a capping agent oleic acid. Varying the concentration of the surfactant and the capping agent has been found to critically govern the nature of the nanoparticles prepared. It is observed that at an optimum concentration of SDS and oleic acid, nearly monodisperse Ni nanoparticles are obtained that form highly ordered hexagonally close-packed structures on electron microscopy grids by a simple drop coating procedure. It is also shown that the presence of oleic acid is necessary for the stability of the Ni nanoparticles synthesized. Structural and magnetic characterizations of the nanoparticles are also presented.

Real-time nanomechanical and topographical mapping on live bacterial cells-brevibacterium casei under stress due to their exposure to Co2+ Ions during microbial synthesis of Co3O4 nanoparticles - Kumar, Umesh; Vivekanand, K.; Poddar, Pankaj (Journal of Physical Chemistry B, 2009)
The study of elastic properties of microbial and mammalian cells using atomic force microscopy, with force-sensitivity as high as pico-Newtons and spatial resolution of a few nanometers, is proving to be a great tool for the real-time observation of the effects of drugs, biomolecules, metal ions, and nanoparticles on cell physiology in their natural environment. It has been shown that the Young's modulus of the cell surfaces is extremely sensitive to the surrounding environment. Recently, a broad array of microbes have been used successfully to synthesize nanocrystals of several metal and metal oxides in a controlled manner at room temperature after exposing them to various metal ion precursors. However, so far there is no report on the fate of their elastic properties and cell topography etc. during and after their exposure to the metal ions during the microbial synthesis of nanomaterials. Additionally, this information is also found to be extremely relevant to areas such as bioremediation, bioleaching, and biomineralization, where it is important to study the direct influence on the cell physiology in the presence of metal ions. Here, we report, for the first time, the use of AFM force-distance curves on live cells, to directly monitor (in real time) the changes in the surface-topography, surface-adhesion, indentation-depth, and Young's modulus of a metal-tolerant marine bacterium, Brevibacterium casei, isolated from the coast of the Arabian Sea, after its exposure to the Co2+ ions during the process of biosynthesis of nanoparticles. We earlier reported that this bacterium is capable of using the cobalt acetate as a precursor to synthesize protein-functionalized Co3O4 nanoparticles with very high crystallinity. Our study indicates a significant change in the morphology as well as elastic and adhesive properties of the Brevibacterium casei, where we found an increase in the adhesive properties and the indentation depth of the bacterial surfaces and a decrease in the cell stiffness after several hours of exposure to the cobalt acetate. We have discussed both qualitative and quantitative analysis of the force-spectroscopy data in detail.

Effect of reduced particle size on the magnetic properties of chemically synthesized BiFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Here, we report the effect of reduction in particle size on the temperature dependent magnetization of chemically synthesized BiFeO3 nanocrystals with average grain size of 55 nm. The X-ray photoelectron spectroscopy results show a significant broadening of binding energy peaks associated to Fe3+ 2p(3/2) core levels due to the reduced size. Additionally, due to the nanosize effect, the M-H loops show a significant coercivity starting from 390 K with an anomaly located in the vicinity of 150 K in our H-c vs T as well as M-r/M-s(50 kOe) vs T curves. At this temperature, both H-c and M-r/M-s(50 kOe) undergo minima. Additionally, our results for the first time show the evidence of existence of a low temperature anomaly due to spin-glass transition in the range from 40-44 K in the field cooled magnetization curves. In bulk single crystals, this transition is reported to be situated at around 50 K, however, this transition remained so far undiscovered in the recent studies on BiFeO3 nanoparticles due to the insufficient temperature resolution. The significant shift in this transition toward lower temperature can be attributed to size dependent effects. Our results clearly present new information on the size dependent properties of BiFeO3 nanoparticles.

Fabrication of homogeneous nanoparticle/nanoneedle BaTiO3 and Ba0.8Sr0.2TiO3 smooth thin films by simple dip coating - Saini, Mamta; Vivekanand, K.; Poddar, Pankaj; Murty, K. V. G. K.; Thushara, K. S.; Gopinath, Chinnakonda S. (International Journal of Nanotechnology, 2010)
Ferroelectric BaTiO3 (BTO) and Ba0.8Sr0.2TiO3 (BSTO) thin film materials have been successfully prepared by sol-gel processing and simple dip coating on glass and silicon supports. Above thin films were characterised by x-ray diffraction (XRD), Raman spectroscopy, photoelectron spectroscopy, thermal analysis, atomic force microscopy (AFM) and spectroscopic ellipsometry. Phase identification of BaTiO3 and Ba0.8Sr0.2TiO3 was performed by XRD. XRD and Raman spectroscopy investigations demonstrate that thc Ba0.8Sr0.2TiO3 film exhibits tetragonal structure. AFM analysis demonstrates the elongated nanospherical particles on glass substrate and nanowires on silicon substrate, which represent a strong influence of the crystallinity of underlying substrate on the grain morphology in this technique. The thin films on both the substrates are uniformly coated without any pinhole to significant area (similar to 2.5 cm(2)), and this method might be extended to large area uniform coating. Spectroscopic ellipsometric measurements reveal the exact thickness, refractive index and extinction coefficient of the thin films.
Keywords: barium strontium titanate; barium titanate; dip coating; fabrication; ferroelectric material; large area coating; nanotechnology; thin film

Magnetic and dielectric properties and Raman spectroscopy of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Maity, Tuhin; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2010)
The rare earth orthochromites are extremely interesting due to the richness of their optical, dielectric, and magnetic properties as well as due to their multiferroic properties which make them suitable materials to study in the nanoregime. However, the wet-chemical synthesis of these materials in nanosize is nontrivial. Here, we report for the first time, the detailed Raman spectra as well as magnetic and dielectric properties of chemically synthesized GdCrO3 nanoparticles of size ranging from 40 to 60 nm. The magnetic properties are dictated by competing Cr3+-Cr3+, Gd3+-Cr3+, and Gd3+-Gd3+ superexchange interactions in different temperature regions, resulting into an antiferromagnetic ordering at 167 K due to the Cr3+-Cr3+ followed by weak ferromagnetic ordering due to the onset of Cr3+-Gd3+ interactions. At lower temperature, it shows weak antiferromagnetic ordering due to Gd3+-Gd3+ interaction. Below 95 K, GdCrO3 nanoparticles showed the presence of negative magnetization due to Gd3+ and Cr3+ interactions resulting into weak ferromagnetic coupling. The Raman spectroscopy shows the characteristic Raman shifts indicating that below 450 cm(-1), Gd3+ ions play a dominant role in determining the phonon frequencies of GdCrO3, and above 450 cm(-1), the Cr+3 ions dominate. We also present for the first time the low temperature dielectric constant and loss tangent data for GdCrO3 in a broad temperature and frequency range. The dielectric constant shows a decrease in comparison to the bulk values due to the size dependent effects. It also shows a peak centered at around 320 K above which it shows a sharp decrease. The dielectric loss value in GdCrO3 nanoparticles is quite small and shows an interesting frequency dependent anomaly at lower temperature which might be due to the coupling between magnetic and dielectric order parameters.
Keywords: dielectric losses; gadolinium compounds; Magnetisation; Multiferroics; nanofabrication; Nanoparticles; permittivity; phonons; Raman spectra; superexchange interactions

Origin of magnetic anomalies below the neel temperature in nanocrystalline LuMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
Rare earth manganites crystallize in distorted orthorhombic perovskite or hexagonal structures and exhibit quite interesting optical and magnetic properties dictated by the size of the rare earth ion. Many of these materials might exhibit both ferroelectric and magnetic ordering as well as magnetoelectric coupling. However, their physical properties at reduced particle sizes remain underexplored due to the challenges associated with their synthesis with a proper control over the crystalline phase. Here, we report the wet-chemical synthesis of the hexagonal phase of nanocrystalline LuMnO3 with an average crystallite size of similar to 32 nm. The room-temperature Raman spectroscopy data are consistent with the calculated values of isomorphous hexagonal RMnO3 (R = rare earth atom) compounds with P6(3)cm symmetry. The UV-vis-NIR spectra recorded in the diffused reflectance mode at room temperature show electronic transitions at 1.7 eV (729 nm), 2.3 eV (539 nm), and 5 eV (258 nm). The magnetization measurements show that the Neel temperature for the LuMnO3 is situated at around 89 K, which is in close proximity to the reported value of the bulk phase. We also observed two unique and field-dependent magnetic anomalies that were predicted earlier but never reported experimentally. The first anomaly is observed as a sharp bifurcation in the ZFC-FC curves below 44 K at a 100 Oe applied field, which is accompanied with a sudden rise in the coercivity and magnetization. A second transition is observed at 12 K as a sharp peak in the ZFC curves, which is accompanied with a dip in coercivity. We attribute the transition at 44 K to the reorientation of the Mn3+ ions due to the Dzyaloshinskii-Moriya interaction, and the transition at 12 K is explained by weak antiferromagnetic coupling between Mn-O-Mn in the ab plane, which becomes dominant at lower temperatures.

Structural, magnetic, and gas adsorption study of a two-dimensional tetrazole-pyrimidine based metal-organic framework - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2010)
A new two-dimensional (2D) metal-organic framework, Cu-TP-1, has been synthesized under solvothermal conditions (DMF) from the transition metal cation Cu(II) and 2-tetrazole pyrimidine (C5H5N6, H-TP). The structure has been determined by single crystal X-ray crystallography which shows a (6,3) honeycomb 2D net with perpendicular one-dimensional channels. Permanent porosity of Cu-TP-1 has been determined by the nitrogen adsorption isotherm. Cu-TP-1 show interesting H-2 and CO2 uptake. CO2 uptake of Cu-TP-1 (at 298 K, 1 atm pressure) is seen to be comparable to the recently reported ZIF-95 which outperforms ZIF-100 and BPL carbon. The magnetic properties show an antiferromagnetically coupled Cu ... Cu interaction down to 8 K with a Weiss temperature around 108 K.

Temperature-dependent raman and dielectric spectroscopy of BiFeO3 nanoparticles: signatures of spin-phonon and magnetoelectric coupling - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Vivekanand, K.; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2010)
We report the temperature-dependent Raman and dielectric spectroscopy of chemically synthesized BiFeO3 nanoparticles (average size similar to 50-60 nm). The Raman spectra (90-700 K) show two sets of transitions in the lowest Raman E mode, associated with Bi-O bond motion situated in close proximity to the spin reorientation transitions reported for BiFeO3, thereby indicating the existence of possible coupling between magnons and phonons for particle size below the helical order parameter (62 nm). These transitions are slightly shifted in temperature in comparison to the bulk single crystals. We also observe a step-like behavior in Raman peak position around the Neel temperature, suggesting that the phonons are influenced by the magnetic ordering in nanosized BiFeO3. The heat-flow measurements show two sharp endothermic peaks at 1094 and 1223 K representing rhombohedral to orthorhombic or monoclinic transition followed by transition into the cubic phase above 1200K. The low temperature (20-325 K), frequency-dependent (1-10(6) Hz) dielectric constant and loss tangent measurements show that the loss tangent (similar to 10(-3)) and ac conductivity values (similar to 10(-8) Ohm(-1)-cm(-1)) are orders of magnitude lower than the reported values for BiFeO3 ceramics, indicating high levels of ionic purity of our samples. The real part of the permittivity shows a slight reduction in its value (similar to 30) in comparison to the bulk single crystals. Similar to the Stokes Raman shift, its temperature-dependent dielectric constant also shows four weak anomalies at similar to 85, 168, 205, and 230 K situated in close proximity to the spin reorientation transitions, indicating magnetoelectric coupling.

Design and in situ synthesis of a Cu-based porous framework featuring isolated double chain magnetic character - Dey, Chandan; Das, Raja; Saha, Binoy Krishna; Poddar, Pankaj; Banerjee, Rahul (Chemical Communications, 2011)
A Cu-based double chain MOF was synthesized in hydrothermal conditions using an in situ ligand formation method. This double chain MOF shows temperature dependent ferromagnetic (long range ordering) and antiferromagnetic (intra double chain) coupling. The magnetic behaviour originating from the individual double chain remains almost same even after structural collapse due to the removal of guest water molecules.

Dielectric and spin relaxation behaviour in DyFeO3 nanocrystals - Jaiswal, Adhish; Das, Raja; Maity, Tuhin; Poddar, Pankaj (Journal of Applied Physics, 2011)
We report the temperature and frequency dependent dielectric measurements and ac magnetic susceptibility of chemically synthesized DyFeO3 nanoparticles (size similar to 50-60 nm). The measurement of the dielectric properties was carried out in a broad temperature (20-325 K) and frequency (1-10(6) Hz) range. The non-Debye type dipolar relaxation phenomenon was observed in the DyFeO3 nanoparticles, as confirmed by the Cole-Cole plots. The higher values of epsilon' at the lower frequencies are explained on the basis of the Maxwell-Wagner model. The Cole-Cole analysis enabled us to separate the contribution of relaxation times, resistance and capacitance in grain and grain boundaries in DyFeO3 nanocrystals. We found that with increasing temperature, the contribution of grain boundary resistance increases in comparison to the grain resistance. We also performed spin relaxation studies in a broad temperature and frequency range. Both the in-phase (chi') and out-of-phase (chi `') components of the ac magnetic susceptibilities of the DyFeO3 nanoparticles show a clear evidence at spin reorientation transition around 70K and T-N (Dy) around 4K as reported by us in our earlier study using the dc magnetic behaviour. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3669154]

Effect of particle size and annealing on spin and phonon behavior in TbMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2011)
Interest has grown to study TbMnO3 as it was recently reported to show a gigantic magnetoelectric effect. Here, we report the synthesis and detailed magnetic and Raman spectroscopy study on TbMnO3 particles of size similar to 25 nm and 2-3 mu m, respectively. The incommensurate-commensurate (lock-in) transition, usually observed at 27 K for bulk phase of TbMnO3 was not observed in susceptibility versus T curve but was seen at 30 K in the coercivity versus T curve in similar to 25 nm particles. This transition, which is due to the spin modulation length scale, gets weakened in nanosize due to the increased intrinsic lattice strain observed in 2-3 mu m particles, due to the effect of increased particle size. The increased value of magnetization in the 2-3 mu m sample was attributed to double exchange interactions between Mn+3 and Mn+4 spins. The role of annealing related effects on the fate of the Neel temperature for TbMnO3 was investigated. Raman spectroscopy indicated a decrease in the lattice distortion for similar to 25 nm particles. (c) 2011 American Institute of Physics. [doi:10.1063/1.3563571]

Field emission studies of silver nanoparticles synthesized by electron cyclotron resonance plasma - Purohit, Vishwas; Mazumder, Baishakhi; Bhise, Ashok B.; Poddar, Pankaj; Joag, Dilip S.; Bhoraskar, S. V. (Applied Surface Science, 2011)
Field emission has been studied for silver nanoparticles (25-200 nm), deposited within a cylindrical silver target in an electron cyclotron resonance (ECR) plasma. Particle size distribution was controlled by optimum biasing voltages between the chamber and the target. Presence of non-oxidized silver was confirmed from the X-Ray diffraction analysis; however, thin protective layer of oxide was identified from the selective area electron diffraction pattern obtained with transmission electron microscopy. The silver nanoparticles were seen to exhibit hilly pointed like structures when viewed under the atomic force microscopy (AFM). The emissive properties of these particles were investigated by field emission microscopy. It is found that this technique of deposition is ideal for formation of nanoparticles films on different substrate geometries with size controllability as well as its application to emission devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cold plasma; field emission; Nanoparticles; thin film

Investigations of magnetic and dielectric properties of cupric oxide nanoparticles - Bhalerao-Panajkar, Rohini S.; Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, S. K. (Solid State Communications, 2011)
Cupric oxide nanoparticles of similar to 8-10 nm width and 40-45 nm length self assembled as large particles similar to 1-1 5 mu m have been investigated in the 10-325 K temperature range using magnetic and dielectric measurements In magnetic measurements a single broad peak at similar to 230 K in a zero field cooled sample has been observed Coercivity in magnetization measurements at 10 K suggests that the nanoparticles are core-shell type particles with an antiferromagnetic core and a ferromagnetic shell Dielectric measurements at various frequencies from 3 7 Hz to 949 kHz exhibit a sharp peak at 284 K followed by weak anomalies around 213 and 230 K (C) 2010 Elsevier Ltd All rights reserved
Keywords: CuO nanoparticles; Dielectric; Ferroelectric transition; Ferromagnetic

Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO

Solvothermal synthesis, structure, and properties of metal organic framework isomers derived from a partially fluorinated link - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Solvothermal reactions of Cu(NO3)(2) center dot 3H(2)O with 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba) and terminal monodentate ligand 3-methyl pyridine (3-picoline/3-mepy) in the presence of N, N-dimethyl formamide (DMF) and N,N-diethyl formamide (DEF) solvents gave rise to two structurally different two-dimensional (2D) fluorinated metal organic frameworks (F-MOFs). The effect of the choice of solvent has been clearly reflected in the structures obtained. The F-MOFs reported in this paper are formulated as [Cu-2(hfbba)(2)(3-mepy)(2)] center dot (DMF)(2)(3-mepy) (F-MOF-4), [Cu-2(hfbba)(2)(3-mepy)(2)] (Cu-F-MOF-4B), and [Zn-2(hfbba)(2)(3-mepy)(2)] center dot (3-mepy) (Zn-F-MOF-4B) which displays interesting 2D structures with and without interdigitation depending on the solvent used. The structures of these F-MOFs have been determined by X-ray crystallography and further identified by IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). The effect of interdigitation has been reflected in the gas adsorption and magnetic properties of these F-MOFs. These F-MOFs also show comparable H-2 and CO2 uptake depending on their structural variation. Temperature-dependent magnetic susceptibility measurements over a wide range of temperatures exhibit dominantly short-range antiferromagnetic behavior, with weak ferromagnetic behavior showing up at very low temperatures, which is evident from opening of the hysteresis loop with a finite value of coercivity in both F-MOF-4 and Cu-F-MOF-4B. We observed a smaller value of mu(eff) per Cu atom and coercivity in Cu-F-MOF-4B than the F-MOF-4 due to relatively larger distances between the neighboring dicopper paddlewheel secondary building unit.

Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.

Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.

Surface effects on morin transition, exchange bias, and enchanced spin reorientation in chemically synthesized DyFeO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Physical Chemistry C, 2011)
A giant linear magnetoelectric effect was observed by Y. Tokura's group recently in multiferroic DyFeO3, which demands a detailed investigation of its magnetic properties. Additionally, there is little information on the changes of chemical and physical properties of these materials with the reduction in particle size in spite of the potential applications of these materials nanoscale devices. As the wet-chemical synthesis of these materials in nanosize and getting a control over crystallinity and stoichiometry is nontrivial and poses a serious challenge prohibiting the study of their size-dependent properties. Here, we report the synthesis of DyFeO3 nanoparticles using a surfactantless hydrothermal method with a detailed magnetic property measurement. The as-synthesized DyFeO3 nanoparticles showed excellent crystallinitywith average particle size in the range 50-60 nm. The structural analysis indicated that they are of a distorted orthorhombic pervoslcite crystal structure. Detailed dc magnetization measurements in the temperature range of 3-350 K could isolate the presence of Dy3+-Fe3+ and Dy3+-Dy3+ superexchange interactions, which showed up as spin reorientation transitions in various temperature regions due to the differing magnitude of their interactions resulting in continuous rotation of antiferromagnetic component of Fe3+ spins with cooling of the sample. Nanosized DyFeO3 showed spin-reorientation transitions near 315 and 70K due to the Dy3+-Fe3+ interaction accompanied with an opening up of the hysteresis loop followed by antiferromagnetic ordering around 4 K due to a possible Dy3+-Dy3+ interaction. We also observed significant effect of the particle size reduction on the magnetic properties. The main effects seen. by us were in terms of (1) pronounced spontaneous spin reorientation transitions, (2) the absence of Morin transition, and (3) presence of temperature-dependent exchange bias in the DyFeO3 nanoparticles. We present a detailed mechanism to explain these features based on the interplay of Dy3+ and Fe3+ spins as well surface disorder, anisotropy, canting, and so forth.

Synthesis and optical studies of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Nanoparticle Research, 2011)
{Here we report for the first time, a detailed synthesis mechanism of GdCrO3 nanoparticles using a surfactant-less hydrothermal method. We also report a detailed study of their structural and optical properties. The selected area electron diffraction and powder X-ray diffraction studies of GdCrO3 nanoparticles show pure phase and excellent crystallinity with average particle size around 50-60 nm. The structural analysis indicates a distorted perovskite crystal structure with lattice parameter values of a = 5.3099 +/- A 0.0022
Keywords: hydrothermal; Nanoparticles; Rare earth orthochromites

Bistable dynamic coordination polymer showing reversible structural and functional transformations - Nagarkar, Sanjog S.; Das, Raja; Poddar, Pankaj; Ghosh, Sujit K. (Inorganic Chemistry, 2012)
A bistable dynamic coordination polymer [Ni(pca)(bdc)(0.5)(H2O)(2)] having a two-dimensional (2D) zigzag sheet structure is synthesized solvothermally. Topological analysis revealed that the frameworks have an hcb type of uninodal net. The compound exhibits guest specific reversible structural transformations accompanying reversible changes in physical properties driven by inherent flexibility and transformability.

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Metal and metal oxide nanoparticle synthesis from metal organic frameworks (MOFs): finding the border of metal and metal oxides - Das, Raja; Pachfule, Pradip; Banerjee, Rahul; Poddar, Pankaj (Nanoscale, 2012)
Herein, for the first time, we report a generalized strategy for the successful synthesis of highly crystalline metal and metal oxide nanoparticles embedded in a carbon matrix by the controlled thermolysis of metal organic frameworks (MOFs). The rationalized synthesis strategy of a broad range of metal and metal oxides nanoparticles, such as Cu/CuO, Co/Co3O4, ZnO, Mn2O3, MgO and CdS/CdO, by thermolysis of MOFs demonstrates for the first time that metal ions with a reduction potential of -0.27 volts or higher present in MOFs always form pure metal nanoparticles during thermolysis in N-2, whereas metal ions with a reduction potential lower than -0.27 volts form metal oxide nanoparticles during thermolysis in N-2. Another point of interest is the fact that we have found a unique relationship between the nanoparticle size and the distance between the secondary building units inside the MOF precursors. Interestingly, the crystallinity of the carbon matrix was also found to be greatly influenced by the environment (N-2 and air) during thermolysis. Moreover, these nanoparticles dispersed in a carbon matrix showed promising H-2 and CO2 adsorption properties depending on the environment used for the thermolysis of MOFs.

Observation of enhanced dielectric coupling and room-temperature ferromagnetism in chemically synthesized BiFeO3@SiO2 core-shell particles - Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Physical Chemistry C, 2012)
We report the effect of SiO2 coating on the structural, magnetic, and dielectric properties of chemically synthesized high-purity BiFeO3 particles. The assynthesized BiFeO3 particles demonstrate properties comparable with those reported for bulk BiFeO3. On the other hand, the structural measurement on BiFeO3@SiO2 shows that the SiO2 coating has anisotropically compressed the lattice of BiFeO3 particles and stimulates the variation in the electron density. This affects magnetic and dielectric behavior of material. Frequency-dependent dielectric constant study at low temperature (20-325 K) revealed slight reduction (8-10%) in the dielectric constant of BiFeO3@SiO2 particles compared to uncoated BiFeO3 particles. The study reveals five anomalies at 234, 206, 146, 84, and 25 K located in close proximity to the linear magnetodielectric coupling and spin reorientation transitions. The loss tangent (approximate to 10(-3)) and alternating current (ac) conductivity (approximate to 10(-8) Omega(-1)cm(-1)) of BiFeO3@SiO2 particles are orders of magnitude lower than those observed for the BiFeO3 particles. The magnetic measurement shows the existence of room-temperature ferromagnetism in BiFeO3@SiO2 particles with average value of magnetic moment per Fe atom approximate to 0.030 mu(B) and appreciable coercivity as high as 120 Oe. The canted spin structure in the surface shell of BiFeO3@SiO2 particles show an enhanced magnetic property and shifted hysteresis loop. The magnetic measurement in close proximity to dielectric transitions revealed enhanced magnetization, suggesting the presence of anisotropies. It has been observed that SiO2 coating alters the properties of BiFeO3 particles. Our dielectric and magnetic measurements show enhanced coupling among the electric and magnetic ordered parameters in BiFeO3@SiO2 core-shell particles compared to uncoated BiFeO3 particles. The magnetic and dielectric properties of SiO2-coated BiFeO3 are similar to nanoparticles of BiFeO3 where interface plays a significant role.

Photopatternable nano-composite (SU-8/ZnO) thin films for piezo-electric applications - Kandpal, Manoj; Sharan, Chandrashekhar; Poddar, Pankaj; Prashanthi, K.; Apte, Prakash R.; Rao, V. Ramgopal (Applied Physics Letters, 2012)
Photo-curable nanocomposite material was formulated by embedding ZnO nanoparticles into a SU-8 matrix and studied for its piezoelectric properties for low cost fabrication of self-powered nanodevices. The piezoelectric coefficient of ZnO nanoparticles was observed to be ranging between 15 and 23 pm/V, which is the highest reported. These experimental studies support the recent theoretical predictions where the piezoelectric coefficients in ZnO nanoparticles were found to be higher compared to the thin films because of the surface relaxation induced volume reductions in the nanometer scale. The photo-curable property of these polymer composite films is exploited to demonstrate fabrication of a micro-cantilever test structure. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748575]

Solid phase morphological diversity of a rare vanadium cubane (V4O16) based metal organic framework - Dey, Chandan; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2012)
A Cu(II) connected V4O16-cubane based metal organic framework, Cu-2(phen)(2)(V4O8) (PO4)(4) [Cu2V4O16-2D] was synthesized under hydrothermal conditions. This is the first example of transition metal connected V4O16-cubane based MOF. X-ray single crystal data shows the alternate arrangement V4O16-cubane and Cu(phen)(O)(3) square pyramidal unit in two dimensions. These two-dimensional sheets are stacked on top of each other to form a three-dimensional architecture. Cu2V4O16-2D shows two types of solid state morphologies of the same phase, which was confirmed by scanning electron microscopy. It is noteworthy that this type of morphological difference of the solid phase in an extended metal organic hybrid material is rare and has not been perceived in the polyoxovanadate based MOFs literature. Cu2V4O16-2D was further characterized by powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), IR-spectroscopy, scanning electron microscopy (SEM), and elemental analysis. We also studied the static magnetic and gas adsorption properties for Cu2V4O16-2D.

Synthesis, characterization, and magnetic studies of coordination polymers with Co(II) and Mn(II) ions - Ahmad, Musheer; Das, Raja; Lama, Prem; Poddar, Pankaj; Bharadwaj, Parimal K. (Crystal Growth & Design, 2012)
{An ether bridged tricarboxylic acid ligand, 5-(4-carboxybenzyloxy)isophthalic acid (p-cbiaH(3)) has been used to construct three coordination polymers with Co(II) salts in presence of different nitrogen donor ligands such as 1,4-bis(4-pyridinylmethyl)piperazine (bpmp), dipyridine-4-yl-diazene (dpd), and 4,4'-bipyridine (bpy). The products formed under hydrothermal conditions are formulated as {[Co-3(p-cbia)(2)(bpmp)(2)(H2O)(6)]center dot 10H(2)O}(n) (1), {[Co-2(p-cbiaH)(2)(dpd)(H2O)(2)]\

Temperature-dependent spectroscopic evidences of curcumin in aqueous medium: a mechanistic study of its solubility and stability - Jagannathan, Ramya; Abraham, Priya Mary; Poddar, Pankaj (Journal of Physical Chemistry B, 2012)
In curcumin, keto-enol-enolate equilibrium of the heptadiene-dione moiety determines its physiochemical and antioxidant properties. However, its poor solubility in water at neutral pH and room temperature decreases its bioavailability. Potential therapeutic applications have triggered an interest in manipulating the solubility of curcumin in water as its stability and solubility in water remains poorly understood. Here, the mechanism behind its solubility at various temperatures and the influence of interplay of temperature, intramolecular H-bonding, and intermolecular forces is reported, which leads to aggregation-disaggregation at various temperatures. Remarkable change is observed in temperature-dependent electronic transition behavior of curcumin, however, the absorption spectra after cooling and heating cycles remain unchanged, hinting much better thermal stability of curcumin in water than previously thought. This study indicates that it is perhaps the breaking of intramolecular hydrogen bonding which leads to exposure of polar groups and hence responsible for the dissolution of curcumin at higher temperature. The formation of intermolecular aggregates might be responsible behind a better room temperature stability of the molecules after cooling its aqueous suspension from 90 to 25 degrees C. These curcumin solubility studies have great application in biological research with reference to bioavailability and to understand target oriented mode of action of curcumin.

Extracellular biosynthesis of water dispersible, protein capped Mn5O8 nanoparticles using the fungus fusarium oxysporum and study of their magnetic behavior - Uddin, Imran; Poddar, Pankaj (Journal of Nanoengineering and Nanomanufacturing, 2013)
Nanomaterials of different sizes, shapes and compositions are being synthesized by various chemical, physical and biological routes. The pressing need of the hour is to have a synthesis protocol which does not harm the environment in any way and is inexpensive so that the benefits can be reaped by all. In this regard, the biological synthesis routes weigh over the chemical and physical ones which are toxic and expensive respectively. The biological routes occur at ambient conditions of temperature, pressure and pH and help protect the ecosystem as these do not employ any hazardous chemicals. Moreover, the nanoparticles obtained via biological routes are naturally protein capped which prevents their agglomeration and helps them retain their shape, size and stability for several months. One such important material is manganese oxide (Mn5O8) which at the nanoscale, has found good use in catalysis and as ionic conductors in fuel cells or batteries. The compound Mn5O8 exists in mixed valences of Mn2+ and Mn4+ and has drawn attention due to its antiferromagnetic nature. Here we report extracellular biosynthesis of manganese oxide (Mn5O8 nanoparticles in the size range of 10–11 nm at room temperature by challenging the fungus Fusarium oxysporum with manganese (II) acetate tetrahydrate [(CH3CO2)2 Mn · 4H2O] as precursor. The Mn5O8 nanoparticles so formed were characterized by TEM, XRD, FTIR, XPS, and TGA. Two mixed manganese ion valencies (Mn2+ and Mn4+) of Mn5O8 have been confirmed by XPS studies and antiferromagnetic transitions by magnetic measurements.

Growth of oriented single crystalline La-doped TiO2 nanorod arrays electrode and investigation of optoelectronic properties for enhanced photoelectrochemical activity - Sadhu, Subha; Poddar, Pankaj (RSC Advances, 2013)
Fabrication of single crystalline, oriented one-dimensional (1D) rods or wires of titania on transparent conducting oxide (TCO) substrates have enormous significance in the area of photoelectrochemical research owning to their unique optoelectronic properties. It is possible to modify the electrical conductivity and optoelectronic properties of titania by intentional inclusion of atomic impurity in the material. Here for the first time, we have doped lanthanum homogeneously in TiO2 nanorod arrays. The homogeneous distribution of lanthanum in titania lattice is confirmed by scanning transmission electron microscopy (STEM) elemental mapping and line scanning analysis. After doping with lanthanum, there is a negative shift of the flat-band potential of the TiO2 nanorods and the charge carrier density of the nanorods is also improved. The energy-conversion efficiency of a dye-sensitized solar cell based on 4 mol% La-doped nanorods is increased about 21% compared with the undoped one.

In situ synthesis and surface functionalization of gold nanoparticles with curcumin and their antioxidant properties: an experimental and density functional theory investigation - Singh, Dheeraj K.; Jagannathan, Ramya; Khandelwal, Puneet; Abraham, Priya Mary; Poddar, Pankaj (Nanoscale, 2013)
Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is an active component of turmeric; it is responsible for its characteristic yellow color and therapeutic potential, but its poor bioavailability remains a major challenge. In order to improve the bioavailability of curcumin, various approaches have been used. One of the possible approaches to increase the bioavailability of curcumin is its conjugation on the surface of metal nanoparticles. Therefore, in the present study, we report the binding of curcumin on the surface of gold nanoparticles (AuNPs). The AuNPs were synthesized by the direct reduction of HAuCl4 using curcumin in the aqueous phase, without the use of any other reducing agents. We found that curcumin acts both as a reducing and capping agent, stabilizing the gold sol for many months. Moreover, these curcumin-capped AuNPs also show good antioxidant activity which was confirmed by the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical test. Thus, the surface functionalization of AuNPs with curcumin may pave a new way of using the curcuminoids towards possible drug delivery and therapeutics. Apart from the experimental study, a detailed quantum chemical calculation using density functional theory (DFT) has been performed, in order to investigate the formation of a complex of curcumin with Au3+ ions in different possible conformational isomeric forms. Our theoretical calculations indicate the evidence of electron transfer from curcumin into the Au center and essentially indicate that as a consequence of complexation, Au3+ ions are reduced to Au-0. Our theoretical results also propose that it is the breakage of intramolecular H-bonding that probably leads to the increased availability of curcumin in the presence of gold ions and water molecules.

Novel green bio-milling technique for the synthesis of BaTiO3 nanoparticle using Saccharomyces cerevisiae - Uddin, Imran; Jaiswal, Adhish; Poddar, Pankaj (International Journal of Innovative Biological Research, 2013)
The development of a novel green top-down approach called bio-milling for synthesizing the oxide nanomaterials is an issue of topical interest. While a number of chemical processes are energy intensive and involve toxic chemicals. Here we report, at room temperature, bio-milling of chemically synthesized barium titinate (BaTiO3) particles by challenging the fungus Saccharomyces cerevisiae against aqueous solution of BaTiO3 to synthesize the biogenic nanoparticles. The extracellular breaking of microscaled BaTiO3 particles by extracellular biomolecules/proteins secreted by the fungus under stressed condition results in the formation of particles in nanoregime. XRD spectra and TEM analysis showed that BaTiO3 particles reduce to their size during the interaction with the fungus Saccharomyces cerevisiae and maintaining their phase and crystallinity after bio-milling process.

Probing interaction of Gram-positive and Gram-negative bacterial cells with ZnO nanorods - Jain, Aanchal; Bhargava, Richa; Poddar, Pankaj (Materials Science & Engineering C-Materials for Biological Applications, 2013)
In the present work, the physiological effects of the ZnO nanorods on the Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Aerobacter aerogenes) bacterial cells have been studied. The analysis of bacterial growth curves for various concentrations of ZnO nanorods indicates that Gram positive and Gram negative bacterial cells show inhibition at concentrations of similar to 64 and similar to 256 mu g/mL respectively. The marked difference in susceptibility towards nanorods was also validated by spread plate and disk diffusion methods. In addition, the scanning electron micrographs show a clear damage to the cells via changed morphology of the cells from rod to coccoid etc. The confocal optical microscopy images of these cells also demonstrate the reduction in live cell count in the presence of ZnO nanorods. These, results clearly indicate that the antibacterial activity of ZnO nanorods is higher towards Gram positive bacterium than Gram negative bacterium which indicates that the structure of the cell wall might play a major role in the interaction with nanostructured materials and shows high sensitivity to the particle concentration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Confocal; Growth curve; Nanorods; SEM; Zeta potential; ZnO

Static and dynamic magnetic properties and effect of surface chemistry on the morphology and crystallinity of DyCrO3 nanoplatelets - Gupta, Preeti; Bhargava, Richa; Das, Raja; Poddar, Pankaj (RSC Advances, 2013)
In this contribution, the structural and magnetic properties of DyCrO3 nanoplatelets, synthesized by a hydrolytic sol-gel method, have been investigated. The crystalline phase of DyCrO3 was attained at the decomposition temperature of 800 degrees C for citric acid and oxalic acid, respectively and their structural analysis indicates a distorted orthorhombic perovskite structure of the DyCrO3 nanoplatelets. The dc-magnetization curve shows the Neel temperature of similar to 144 and similar to 146 K for DyCrO3 nanoplatelets synthesized using citric acid (DCO (C)) and oxalic acid (DCO (O)), respectively. In addition, DCO (O) shows weak anomalies at similar to 22 and similar to 6 K in the zero-field-cooled and field-cooled magnetization curves. Below the Neel temperature, DCO (C) and DCO (O) exhibit cross-over from positive to negative magnetization at similar to 143 and similar to 145 K, respectively. This was attributed to a Dy3+-Cr3+ interaction, which resulted in a weak ferromagnetic coupling (seen as a small opening in the M-H curves). The low temperature transition observed at similar to 6 K can be assigned to the onset of Dy3+-Dy3+ antiferromagnetic interaction.

Static and dynamic magnetic properties and interplay of Dy3+, Gd3+ and Mn3+ spins in orthorhombic DyMnO3 and GdMnO3 nanoparticles - Das, Raja; Jaiswal, Adhish; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2013)
Single-phase orthorhombic DyMnO3 and GdMnO3 nanoparticles in the size range 60-70 and 35-45 nm, respectively, were synthesized using a modified hydrothermal method. The magnetic property measurements of DyMnO3 nanocrystals show anomalies around similar to 43K (antiferromagnetic (AFM) coupling between Mn3+ spins) and at 7K in the form of a peak in the zero-field-cooled curve (AFM coupling between Dy3+ spins). Whereas, GdMnO3 undergoes a phase transition at similar to 42K from paramagnetic to an incommensurate-antiferromagnetic phase (ICAFM) followed by a second anomaly at similar to 22 K, which could be associated with the transition from ICAFM into a canted A-type AFM ordering of the Mn3+ spins. This transition is followed by a long-range ordering of the Gd3+ moments at 6K yielding the canting of the Gd3+ spins with a ferromagnetic (FM) component antiparallel to the FM moment of the canted Mn3+ spins. No anomaly near the Neel temperature of the Mn moments for both DyMnO3 and GdMnO3 nanoparticles was observed in ac magnetization which were observed in dc magnetization. The room temperature Raman spectra of DyMnO3 shows two most intense Raman modes at 480 and 609 cm(-1) which can be assigned to an antisymmetric Jahn-Teller stretching mode and a symmetric or breathing stretching mode, respectively, involving Mn-O bond stretching.

Surface chemistry and growth mechanism of highly oriented, single crystalline TiO2 nanorods on transparent conducting oxide coated glass substrates - Sadhu, Subha; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (RSC Advances, 2013)
The fabrication of one-dimensional (1D) rods or wires of titania in desired crystalline facets is quite exciting due to unique optoelectronic properties. The single crystalline, oriented nanorods directly grown on transparent conducting oxide (TCO) substrates are finding a lot of interest in solar photovoltaics and several other optoelectronic devices due to enhanced electron transport and lower exciton recombination rates. However, the growth of desired crystalline facets of highly oriented, single crystalline nanorods on different substrates and understanding the interplay between the surface chemistry and growth mechanism still remain a non-trivial and challenging task. Here, for the first time, the kinetically controlled growth of the (310) facet of TiO2 nanorods on fluorine-doped tin oxide (FTO) coated glass substrate has been reported which is in contrast to the previously reported (002) faceted TiO2 nanorods. In addition to this, the growth of (110) facet TiO2 nanorods using amorphous fluorine doped silicon oxide (FSO) as a substrate is also demonstrated. In this paper, it is shown that two different faceted TiO2 nanorods can be synthesized following same synthetic condition by varying only the material properties of the substrate. To investigate the role of substrate chemistry on the morphology and single crystallinity of TiO2 nanorods, electron microscopy, XPS and contact angle measurements have been done. The results clearly indicate an important link between the surface chemistry and morphology of TiO2 nanorods. It can be assumed that there is a role of OH- and water groups which are responsible for the growth of plane (110) which has less surface energy. The observation of (310) facet is quite surprising and can be explained based on FTO crystallinity. It is possible to tune the diameter of the titania nanorods by further coating the FTO substrate with a thin gold layer due to increase in the hydrophilicity of the substrate. Finally, a light to electricity conversion efficiency of 2.5% could be achieved by using vertically grown titania nanorods on FTO as the photoanode in a dye sensitized solar cell (DSSC).

Interchain relay of antiferromagnetic ordering in 1D Co(II) coordination polymers via pi-pi interactions - Ahmad, Musheer; Das, Raja; Mrozinski, Jerzy; Bienko, Alina; Poddar, Pankaj; Bharadwaj, Parimal K. (CrystEngComm, 2014)

Ionic control on the morphology of ytterbium manganese oxide nanorods and nanoplates in a surfactant-free synthesis and their magnetic properties - Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Here, we report the synthesis of multiferroic, single-crystalline ID YbMnO3 in nanoregime. By using ionic chemistry without the use of surfactant or template, we demonstrate control synthesis of one- and two-dimensional nanoparticles of YbMnO3. Magnetic properties of YbMnO3 show influence of morphology. Detailed alternating current (ac) and direct current (dc) magnetic study shows ferromagnetic interaction of Mn3+ and Yb3+ moments in nanorods of YbMnO3 below similar to 35 K.

Large increase in the energy product of Fe3Se4 by Fe-site doping - Sen Bishwas, Mousumi; Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Fe3Se4 possesses a large coercivity at room temperature. At lower temperature, a coercivity value up to 40 kOe has been achieved. However, due to a relatively lower saturation magnetization value, the energy product of this material is not suitable for its use as rare-earth-free hard magnetic material. Although the anisotropy and magnetic structure of Fe3Se4 have been topics of research, there is no attempt to increase the energy product. Here, we report the synthesis of Fe3-xMnxSe4 (x = 0.01-0.2) nanorods. As required for practical applications, after doping, the Curie temperature remains unchanged; however, at optimum (x = 0.03) doping of manganese ions, the magnetization of the host matrix increases significantly from 4.84 to 7.54 emu/g. The corresponding energy product value was found to be increased by more than 130%. At low temperature (10 K) the energy product shows almost a 2 order of magnitude increase (similar to 0.12 MG Oe), which makes it valuable for many low temperature applications. This improvement is a vital step for its use in some of the household applications where a large volume and relatively lower energy product are needed.

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic

Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Modulation of reaction kinetics for the tuneable synthesis of gold nanoparticles and quantum clusters: application of gold quantum clusters as ``turn-off'' sensing probe for Sn4+ ions - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (ChemPlusChem, 2014)
The syntheses of gold nanoparticles (Au NPs) and gold quantum clusters (Au QCs) that employ cefadroxil (CFX; an antibiotic) as both reducing and capping agents are reported. The HAuCl4/CFX concentration, temperature, and pH are crucial factors in the modulation of the nucleation and growth kinetics of the reaction, and consequently, in guiding the size and morphology of as-synthesized Au NPs. Interesting results are observed if the reaction is performed under different pH conditions. TEM analysis of the Au NPs synthesized at pH 6 shows an average particle size of approximately 2 nm along with a relatively smaller population of bigger NPs (up to 6 nm). The Au QCs were isolated by high-speed centrifugation and showed fluorescence at lambda approximate to 460 nm. Furthermore, the as-synthesized Au QCs were applied as sensor for Sn4+ ions on the basis of an aggregation-induced fluorescence quenching mechanism. These Au QCs offer acceptable sensitivity, high selectivity, and a limit of detection of approximately 10 mm for the determination of Sn4+ ions.

Observation of exchange bias below incommensurate antiferromagnetic (ICAFM) to canted A-type antiferromagnetic (cAAFM) transition in nanocrystalline orthorhombic EuMnO3 - Das, Raja; Poddar, Pankaj (RSC Advances, 2014)
Detailed ac and dc magnetic properties of orthorhombic EuMnO3 were studied using a nanocrystalline powder sample. Orthorhombic EuMnO3 nanoparticles of 45 nm average size were synthesised using a hydrothermal method. Zero field cooled (ZFC) and field cooled (FC) magnetisation shows anomalies at similar to 53, 44 and 24 K attributed to paramagnetic (PM) to an incommensurate antiferromagnetic phase (ICAFM), ICAFM to a canted A-type antiferromagnetic order (cAAFM) and spin reorientation transitions, respectively. No indication of a PM to ICAFM transition was observed in either the real or imaginary part of ac magnetisation. The real part of the ac magnetisation curve showed a peak at similar to 24.7 K and anomalies at similar to 46.8 and 21.8 K were observed in the imaginary part of ac magnetisation. Reduction in the width of the thermal hysteresis between the field cooling and heating magnetisation curve was observed with the nanocrystallites (similar to 1 K) compared with the bulk phase (similar to 3 K) EuMnO3. Isothermal magnetisation showed a large value of the exchange bias (2799 Oe at 3 K) below the ICAFM to cAAFM transition temperature.

Static and dynamic photoluminescence and photocatalytic properties of uniform, monodispersed up/down-converting, highly luminescent, lanthanide-ion-doped beta-NaYF4 phosphor microcrystals with controlled multiform morphologies - Padhye, Preeti; Poddar, Pankaj (Journal of Materials Chemistry A, 2014)
Lanthanide-ion-doped, single-crystalline hexagonal phase NaYF4 microcrystals with multiform morphologies, such as microrods, hexagonal microprisms, and spindle-like structures, were fabricated via a cationic/anionic binary capping agent system: CTAB and a tri-sodium citrate-assisted hydrothermal route. The influence of synthesis conditions on the crystalline morphology was studied and the possible growth mechanisms are presented systematically. The down-conversion and up-conversion photoluminescence (PL) properties of beta-NaYF4:Ln(3+) (Ln = Tb, Yb/Er, and Yb/Tm) were investigated. The static and dynamic PL studies of beta-NaYF4:5% Tb3+ showed strong dependence of luminescent properties on the crystalline morphology. Furthermore, the beta-NaYF4:5% Tb3+ phosphors exhibited efficient photocatalytic activity under UV as well as solar light irradiation, and showed enhanced selectivity towards methylene blue. Moreover, the morphological effect on the photocatalytic activity of beta-NaYF4:5% Tb3+ crystals has also been studied. The high luminescence efficiency and strong photocatalytic activity of beta-NaYF4:5% Tb3+ make them a potential phosphor material and promise to provide a gateway into other applications as in biology and materials sciences.

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Template-free fabrication of highly-oriented single-crystalline 1D-rutile TiO2-MWCNT composite for enhanced photoelectrochemical activity - Sadhu, Subha; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Template-free synthesis of phase pure one-dimensional (1D), single crystalline rutile titania nanorods or wires at low temperature still remains a challenging task due to its complex nature of surface chemistry. In these ID structures, charge transport is highly favored. To further modify the electrical conductivity and optoelectronic properties of these 1D nanostructures, various methods such as doping of TiO2 with metal and nonmetal and synthesis of branched and hybrid structures are developed. If these hybrid structures can directly synthesize on the substrate, the transport of the electron will improve due to reduced grain boundary and exciton recombination. In this contribution, for the first time, we have simultaneously synthesized 1D-rutile TiO2-multiwalled carbon nanotube (MWCNT) composite film directly grown on fluorine dope conducting oxide (FTO) substrate along with 1D-rutile TiO2-MWCNT composite powder. The as-grown nanorods films were single-crystalline and oriented vertically with respect to the substrate, having an average height of similar to 2 mu m. The well connected network of TiO2 with MWCNTs was observed through electron microscopy. The composite film shows positive movement of the flat-band edge and increase in charge carrier density. The TiO2-MWCNT composite was successfully used as photoanode in a dye sensitized solar cell (DSSC) and exhibits a 60% increase in energy-conversion efficiency compared with only TiO2 nanorods.

Biomilling of rod-shaped ZnO nanoparticles: a potential role of saccharomyces cerevisiae extracellular proteins - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
There is a tremendous interest in newly-discovered, green, room-temperature, biological routes for the fabrication of biologically-benign functional nanostructures. The bottom-up biogenic synthesis, where the precursor molecules form crystalline solids at the nanoscale by a redox process, has been validated over the years and gained its popularity. However, a new top-down technique has recently been developed by our group, in which small isotropic nanoparticles (NPs) are formed by the break-down of chemically-synthesized anisotropic rod or plate-shaped NPs using microbes (termed as biomilling). This technique, which holds great promise, is still in its infancy. Here, an improved process with an easy isolation of NPs from the biomass and better control of the technique is reported. This novel technique is demonstrated to break-down the chemically synthesized ZnO nanorods (NRs), similar to 250 nm in length, to small quasi-spherical ZnO NPs (similar to 10 nm in diameter) possibly due to the proteins secreted by the yeast (Saccharomyces cerevisiae), which also led to the formation of `` corona'' around the NPs. The UV-vis, PL and FTIR results show the dynamic nature of the protein corona, which is further supported by the SDS-PAGE study of the extracellular proteins. The SDS-PAGE study of the intracellular proteins shows the over-expression of a single protein which is supposed to have a role in zinc transport in the cells. The ICP-OES results show the accumulation of a higher amount of zinc in the yeast cells as biomilling progresses, while the extracellular zinc contents were almost same. Therefore, we believe that the yeast cells play an important role in the biomilling process by secreting the proteins and maintaining the zinc content in the extracellular fluid. The biomilled NPs exhibit a uniform dispersity and better aqueous stability than chemically synthesized ZnO NRs.

Colossal increase in negative magnetization, exchange bias and coercivity in samarium chromite due to a strong coupling between Sm3+-Cr3+ spins sublattices - Gupta, Preeti; Bhargava, Richa; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2015)
We report giant temperature dependent negative magnetization (magnetization reversal) along with a large exchange bias and large coercivity in SmCrO3. The static magnetization measurements show the negative magnetization below similar to 192 K, due to competition between the external field, thermal activation energy and antiparallel Sm3+-Cr3+ spin interaction. At further lower temperatures, Sm3+ spins show an increased alignment due to the internal induced field of Cr3+ spins with minimum magnetization similar to - 0.037 emu g(-1). The temperature dependent exchange bias shows non-monotonic behavior. At 35 K, the exchange bias ceases to exist due to the orientation of Sm3+ moments with respect to canted Cr3+ moments. The crossover temperature decreases from similar to 191 K at 100 Oe to similar to 153 K at 250 Oe. The training effect further confirms the exchange bias in SmCrO3. The dynamic magnetization measurements exhibit anomalies around spin reorientation transition (T-SR similar to 34 K) and Neel transition (T-N similar to 192 K) which is consistent with static measurement and no frequency dependence was observed. The room temperature Raman spectra of SmCrO3 show peaks at similar to 364, similar to 375 and similar to 456 cm(-1) suggesting O-Cr-O bending modes within the octahedral.
Keywords: exchange bias; multiferroics etc; negative magnetization; samarium chromite; spin reorientation

Construction of polynuclear lanthanide (Ln = Dy-III, Tb-III, and Nd-III) cage complexes using pyridine-pyrazole-based ligands: versatile molecular topologies and smm behavior - Bala, Sukhen; Sen Bishwas, Mousumi; Pramanik, Bhaskar; Khanra, Sumit; Fromrn, Katharina M.; Poddar, Pankaj; Mondal, Raju (Inorganic Chemistry, 2015)
Employment of two different pyridyl pyrazolyl-based ligands afforded three octanudear lanthanide(III) (Ln = Dy, Tb) cage compounds and one hexanudear neodymium(III) coordination cage, exhibiting versatile molecular architectures including a butterfly core. Relatively less common semirigid pyridyl pyrazolyl-based asymmetric ligand systems show an interesting trend of forming polynuclear lanthanide cage complexes with different coordination environments around the metal centers. It is noteworthy here that construction of lanthanide complex itself is a challenging task in a ligand system as soft N-donor rich as pyridyl pyrazol. We report herein some lanthanide complexes using ligand containing only one or two O-donors compare to five N-coordinating sites. The resultant multinuclear lanthanide complexes show interesting magnetic and spectroscopic features originating from different spatial arrangements of the metal ions. Alternating current (ac) susceptibility measurements of the two dysprosium complexes display frequency- and temperature-dependent out-of-phase signals in zero and 0.5 T direct current field, a typical characteristic feature of single-molecule magnet (SMM) behavior, indicating different energy reversal barriers due to different molecular topologies. Another aspect of this work is the occurrence of the not-so-common SMM behavior of the terbium complex, further confirmed by ac susceptibility measurement.

Doxorubicin-conjugated beta-NaYF4:Gd3+/Tb3+ multifunctional, phosphor nanorods: a multimodal, luminescent, magnetic probe for simultaneous optical and magnetic resonance imaging and an excellent pH-triggered anti-cancer drug delivery nanovehicle - Padhye, Preeti; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Sarnit; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report the fabrication of a multifunctional nanoprobe based on highly monodispersed, optically and magnetically active, biocompatible, PEI-functionalized, highly crystalline beta-NaYF4:Gd3+/Tb3+ nanorods as an excellent multi-modal optical/magnetic imaging tool and a pH-triggered intracellular drug delivery nanovehicle. The static and dynamic photoluminescence spectroscopy showed the presence of sharp emission peaks, with long lifetimes (similar to 3.5 milliseconds), suitable for optical imaging. The static magnetic susceptibility measurements at room temperature showed a strong paramagnetic signal (chi similar to 3.8 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed fair T-1 relaxivity (r(1) = 1.14 s(-1) mM(-1)) and magnetic resonance imaging gave enhanced T-1-weighted MRI images with increased concentrations of beta-NaYF4:Gd3+/Tb3+ making them suitable for simultaneous magnetic resonance imaging. In addition, an anticancer drug, doxorubicin (DOX) was conjugated to the amine-functionalized beta-NaYF4:Gd3+/Tb3+ nanorods via pH-sensitive hydrazone bond linkages enabling them as a pH-triggered, site-specific drug delivery nanovehicle for DOX release inside tumor cells. A comparison between in vitro DOX release studies undertaken in normal physiological (pH 7.4) and acidic (pH 5.0) environments showed an enhanced DOX dissociation (similar to 80%) at pH 5.0. The multifunctional material was also applied as an optical probe to confirm the conjugation of DOX and to monitor DOX release via a fluorescence resonance energy transfer (FRET) mechanism. The DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods exhibited a cytotoxic effect on MCF-7 breast cancer cells and their uptake by MCF-7 cells was demonstrated using confocal laser scanning microscopy and flow cytometry. The comparative cellular uptakes of free DOX and DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods were studied in tumor microenvironment conditions (pH 6.5) using confocal imaging, which showed an increased uptake of DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods. Thus, DOX-conjugated beta-NaYF4:Get(3+)/Tb3+ nanorods combining pH-triggered drug delivery, efficient luminescence and paramagnetic properties are promising for a potential multifunctional platform for cancer therapy, biodetection, and optical and magnetic resonance imaging.

Mechanistic insight into the biomilling of goethite (alpha-FeO(OH)) nanorods using the yeast Saccharomyces cerevisiae - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
Since the last decade, eco-friendly routes for the synthesis of nanostructured materials of various types and functionalities have been a topic of enormous interest in the field of nanotechnology. The primary work in this field started with the `bottom-up' microbial synthesis of nanoparticles, however, the bioleaching potential of microbes was initially overlooked in this research. The bioleaching process is useful especially where the synthesis of particles with size < 10 nm is challenging. In the present work, the mechanistic insight of biomilling for a gradual transformation of anisotropic alpha-FeO(OH) rod-shaped particles into isotropic nanoparticles below 10 nm size has been explored using detailed UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopic studies which suggest that the aquo group present at the alpha-FeO(OH) surface may provide the site for interaction with carboxyl ions of protein molecules which results in the formation of a stable coordination compound with Fe3+ ions. This will create a new Fe3+ ion on the surface of the lattice which leads to the repetition of the process of protein complexation with Fe3+ ions and dissociation of the complex from the lattice that causes the fragmentation of bigger nanoparticles into protein functionalized smaller nanoparticles.

Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices

Study of the nucleation and growth of antibiotic labeled Au NPs and blue luminescent Au-8 quantum clusters for Hg2+ ion sensing, cellular imaging and antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report a detailed experimental study supported by DFT calculations to understand the mechanism behind the synthesis of cefradine (CFD - an antibiotic) labeled gold nanoparticles (Au NPs) by employing CFD as both a mild reducing and capping agent. The analysis of the effect of growth conditions reveals that a higher concentration of HAuCl4 results in the formation of an increasing fraction of anisotropic structures, higher temperature leads to the formation of quasi-spherical particles instead of anisotropic ones, and larger pH leads to the formation of much smaller particles. The cyclic voltammetry (CV) results show that when the pH of the reaction medium increases from 4 to 6, the reduction potential of CFD increases which leads to the synthesis of nanoparticles (in a pH 4 reaction) to quantum clusters (in a pH 6 reaction). The MALDI-TOF mass spectrometry results of supernatant of the pH 6 reaction indicate the formation of [Au-8(CFD)(2)S-6] QCs which show fluorescence at ca. 432 nm with a Stokes shift of ca. 95 nm. The blue luminescence from Au-8 QCs was applied for sensing of Hg2+ ions on the basis of an aggregation-induced fluorescence quenching mechanism and offers good selectivity and a high sensitivity with a limit of detection ca. 2 nM which is lower than the detection requirement of 10 nM by the U.S. EPA and 30 nM by WHO for drinking water. We have also applied the sensing probe to detect Hg2+ ions in bacterial samples. Further, we have investigated the antibacterial property of as-synthesized Au NPs using MIC, growth curve and cell survival assay. The results show that Au NPs could reduce the cell survival very efficiently rather than the cell growth in comparison to the antibiotic itself. The scanning electron microscopy study shows the degradation and blebbing of the bacterial cell wall upon exposure with Au NPs which was further supported by fluorescence microscopy results. These Au NPs did not show reactive oxygen species generation. We believe that the bacterial cytotoxicity is due to the direct contact of the Au NPs with bacterial cells.

Temperature and magnetic field-assisted switching of magnetization and observation of exchange bias in YbCrO3 nanocrystals - Gupta, Preeti; Poddar, Pankaj (Inorganic Chemistry, 2015)
In this paper, we demonstrate an interesting feature in YbCrO3 (YCO) nanocrystals, in which the material shows temperature and external magnetic field-assisted switching (a complete sign reversal) of zero field cooled magnetization (M-ZFC) and observation of exchange bias (EB) as a result of competing spin interaction at low temperature. This feature can be applied in nonvolatile memories, where, simply by changing the magnitude of the H-ext and T, the polarity of the magnetization can be switched between negative and positive. We also observed negative magnetization in YCO. Our results showed that, below its Neel temperature (T-N approximate to 119 K), the M-ZFC crosses over to negative sign for H < 1000 Oe. At 60 K, YCO showed a significant negative M-ZFC approximate to -0.05 emu/g (at 100 Oe) due to the competing effects of Yb3+, Cr3+ spins, thermal activation energy, and Hext. At further lower temperatures, the M-ZFC showed a crossover to positive values, and the crossover temperature showed the dependence on H-ext (similar to 19 K for 100 Oe curve). The YCO also showed H-ext T-dependent H-EB, which changed its sign with T. The observed T-dependent sign reversal in the EB was closely associated with the sign reversal of M-ZFC. The symmetric shift in field-cooled isothermal hysteresis curves confirmed that the observed EB was not due to the unsaturated minor loop. The training cycle further confirmed that the H-EB value decreased to similar to 2% of the initial value of observed EB, which was very small compared to the observed H-EB in YCO, which indicated stable spin configuration at the locally formed ferromagnetic/antiferromagnetic interface.

Tunable band gap and coercivity of bismuth ferrite-polyaniline core-shell nanoparticles: the role of shell thickness - Chaturvedi, Smita; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha (RSC Advances, 2015)
We report a tunable band gap of bismuth ferrite-polyaniline core-shell nanoparticles from 2.24 to 1.98 eV and the variation of coercivity from 118 to 100 Oe, by varying the thickness of the polyaniline shell. Bismuth ferrite nanoparticles were synthesized via a chemical route and coating of polyaniline was achieved by a double surfactant layer technique. Coating of polyaniline introduced oxygen vacancies, local distortions and microstrains in the bismuth ferrite lattice which resulted in a change in the Fe-O-Fe bond angle of the bismuth ferrite lattice. This is confirmed with structural analysis tools i.e. X-ray Diffraction, Fourier Transform Infrared Spectroscopy and Raman spectroscopy. Moreover, the absorption of light around 600 nm is increased and photoluminescence emission around 430 nm is decreased, as the thickness of shell is increased, which also indicates the changes in optical properties due to variation in shell thickness. Thus tunability of the band gap and coercivity is achieved as a function of shell thickness in bismuth ferrite-polyaniline core-shell nanoparticles.

Using Raman and dielectric spectroscopy to elucidate the spin phonon and magnetoelectric coupling in DyCrO3 nanoplatelets - Gupta, Preeti; Poddar, Pankaj (RSC Advances, 2015)
In this study, we report the phonon-mode assignment of DyCrO3 nanoplatelets by Raman spectroscopy. The temperature dependent Raman studies indicate the shift in the phonon frequency of most intense modes of DyCrO3 and the observed change in Raman line-width is correlated with the spin-phonon coupling. The impedance spectroscopy reveals anomalies in the dielectric constant vs. temperature curve in the proximity of the magnetic transitions, thereby hinting towards possible weak magnetoelectric coupling in DyCrO3 nanoplatelets. For the first time, UV-vis absorption spectroscopy and photocatalytic activity of DyCrO3 nanoplatelets have been reported. The optical absorption spectrum gives the band gap similar to 2.8 eV for DyCrO3 nanoplatelets suggesting them as a good candidate for studying photocatalytic activity. The DyCrO3 nanoplatelets showed an efficient photocatalytic activity by degrading 65% methyl orange after 8 h irradiation.

Broad spectrum photon responsive, paramagnetic beta-NaGdF4: Yb3+, Er3+ - mesoporous anatase titania nanocomposite - Padhye, Preeti; Sadhu, Subha; Malik, Monika; Poddar, Pankaj (RSC Advances, 2016)
Herein, we report a novel single multifunctional platform based on broad-spectrum photoactive beta-NaGdF4:18% Yb3+, 2% Er3+ and mesoporous anatase TiO2 for enhanced energy and simultaneous biomedical applications. Currently, the photoactive materials for solar energy harvesting applications have limitations in their efficiency due to their narrow photon absorption spectrum. The upconversion phosphor beta-NaGdF4: 18% Yb3+, 2% Er3+ nanorods collect and harvest the NIR photons (similar to 980 nm) of sunlight and transform them into visible light via anti-Stokes emission (lambda(em) similar to 521 and similar to 540 nm), and the photoactive mesoporous anatase TiO2 (mTiO(2)) utilizes UV and weak visible photons, thus the composite forms a broad spectrum photon-capture system and improved power conversion efficiency for enhanced applications in photocatalysis, and dye sensitized solar cells (DSSCs). The photocatalytic activity of the nanocomposite showed an improvement in comparison to the mTiO(2) for the degradation of various dyes. In addition, the photocurrent density and solar cell efficiency of the nanocomposites showed an improvement by similar to 24% and similar to 17% respectively, over mTiO(2). The beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite exhibits a strong paramagnetic signal (chi similar to 6.45 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed large longitudinal T1 relaxivity (r(1) = 7.09 s(-1) mM(-1)) and magnetic resonance imaging showed enhanced T-1-weighted MRI images with increased concentrations of beta-NaGdF4: Yb3+, Er3+/mTiO(2) nanocomposite making them suitable for simultaneous magnetoresonance imaging. In addition, this composite system can also be used as a NIR triggered drug delivery system and in biomedical applications. Moreover, mesoporous TiO2 is expected to increase the photocatalytic active sites, dye, and absorption, and drug loading capacity. The as-designed multifunctional beta-NaGdF4:Yb3+, Er3+/mTiO(2) nanocomposite possessed simultaneous multiple discrete functionalities with excellent luminescence properties, intrinsic paramagnetism, biocompatibility, improved photocatalytic activity, and solar cell efficiency. This work provides a promising system to utilize NIR light, which will contribute to efficient photon harvesting and biological applications.

Immobilization of multivalent glycoprobes on gold surfaces for sensing proteins and macrophages - Gade, Madhuri; Khandelwal, Puneet; Sangabathuni, Sivakoti; Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Poddar, Pankaj; Kikkeri, Raghavendra (Analyst, 2016)
The multivalent display of carbohydrates on the cell surface provides cooperative binding to improve the specific biological events. In addition to multivalency, the spatial arrangement and orientation of sugars with respect to external stimuli also trigger carbohydrate-protein interactions. Herein, we report a non-covalent host-guest strategy to immobilize heptavalent glyco-beta-cyclodextrin on gold-coated glass slides to study multivalent carbohydrate-protein interactions. We have found that the localization of sugar entities on surfaces using beta-cyclodextrin (beta-CD) chemistry increased the avidity of carbohydrate-protein and carbohydrate-macrophage interactions compared to monovalent-beta-CD sugar coated surfaces. This platform is expected to be a promising tool to amplify the avidity of sugar-mediated interactions on surfaces and contribute to the development of next generation bio-medical products.

Study of magnetic and thermal properties of SmCrO3 polycrystallites - Gupta, Preeti; Poddar, Pankaj (RSC Advances, 2016)
In the present work, we have studied the magnetic and thermal properties of sol gel derived samarium chromite (SCO) polycrystallites. The magnetic measurements of SCO polycrystallites show a characteristic antiferromagnetic transition T-N similar to 190 K and spin reorientation temperature T-SR similar to 33 K, which is in the region of interest to study a possible magnetocaloric effect (MCE). The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. The SCO polycrystallites possesses both inverse (positive) and normal (negative) MCE at and above around the spin reorientation transition (TSR) with Delta S-M(max) M values of similar to -24 x 10(-2) & 13 x 10(-2) J kg(-1) K-1, respectively. The SCO also shows another normal (negative) MCE peak around its Neel transition (T-N) with -Delta S-M(max) M similar to 11 x 10(-2) J kg(-1) K-1. The presence of two successive MCE peaks in SCO in the temperature range of 3-50 K, leads to an similar to 47 K operating temperature window with one thermodynamic cycle. In addition, the low temperature heat capacity (C-P) measurements of SCO polycrystallites reveal a lambda-shaped peak at T-N which is associated with a conventional second- order, paramagnetic to antiferromagnetic (AFM), phase transition. The temperature and magnetic field dependence of the specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). In addition the C-P vs. T curve in SCO also shows a weak anomaly around the similar to T-SR along with a Schottky anomaly below 10 K.

Study of magnetic entropy and heat capacity in ferrimagnetic Fe3Se4 nanorods - Sen Bishwas, Mousumi; Poddar, Pankaj (Journal Of Physics D-Applied Physics, 2016)
Change in the magnetic entropy and specific heat capacity in Fe3Se4 nanorods synthesized by a wet-chemical method in a broad temperature (215-340 K) and magnetic field range (0-60 k Oe) was studied. The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. S-M(max) of -46 x 10(-2) J kg(-1).K-1 was obtained at similar to 317 K when the field was changed from 0 to 60 kOe. The maximum in the isothermal magnetic entropy change (Delta S-M) is observed in close proximity to TC (similar to 323 K), which is linked to the order-disorder transition. The nature of this transition was analyzed by universal curve behavior. The temperature and magnetic field dependence of specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). The magnetic entropy change of Fe3Se4 nanoparticles is found to be comparable with similar ferrite and manganite nanoparticle systems and a broad operating temperature window of similar to 30 K was observed around room temperature.
Keywords: heat capacity; iron selenide; Magnetic anisotropy; magnetic entropy; order-disorder phase transition

Fluorescent metal quantum clusters: an updated overview of the synthesis, properties, and biological applications - Khandelwal, Puneet; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
Metal quantum clusters are evolving as excellent systems for a wide range of biological applications due to their small size (similar to 2 nm), tunable optical properties, including optical absorption, photoluminescence (UV to NIR), nonlinear optical properties (two-photon absorption, two-photon fluorescence, and second/third harmonic generation), ultrafast dynamics (relaxation kinetics, electron-phonon coupling, and radiative emission), and magnetism. These excellent properties have resulted in their use in a broad range of applications, including the sensing of ions (heavy metal ions, anions), biomolecules (proteins, DNA, miRNA, and enzymes), biological cells, diagnosis, and therapy. This article presents an introduction to metal quantum clusters, including a brief history of research in this system and an overview of the existing theories to understand their properties. We also discuss the synthesis methods, the various properties of quantum clusters and present a broad and updated overview of the applications of metal quantum clusters in biology.

Growth of flower-like patterns of TiO2 nanorods over FTO substrate - Issar, Sheetal; Poddar, Pankaj; Mehra, N. C.; Mahapatro, Ajit K. (International Conference on Technologically Advanced Materials (ICTAM), 2017)
Nanostructures such as nanoparticles, nanowires, nanorods, nanotubes have attracted great interest with the understanding of shape and size dependence in the electronic and sensing properties. This work demonstrates growth and characterization of one-dimensional nanorods of titanium-dioxide (TiO2) on the fluorine doped tin oxide (FTO) substrate by using hydrothermal method. Field effect scanning electron microscopy shows flower-like morphology, and energy-dispersive X-ray spectroscopy confirms the presence of Ti and O. The X-ray diffraction peaks agree well with the JCPDS data. Initially, the 1D nanorods are formed and high concentration of precursor assists evolution of the short branches to form flower-like structures.

Ln(8) (Ln = Gd, Ho, Er, Yb) Butterfly core-exhibiting magnetocaloric effect and field-induced SMM behavior for Er analouge - Bala, Sukhen; Adhikary, Amit; Bhattacharya, Sudeshna; Sen Bishwas, Mousumi; Poddar, Pankaj; Mondal, Raju (ChemistrySelect, 2017)
In this article, we report four pyridyl-pyrazolyl based poly-nuclear cluster complexes with Ln(8) {Ln = [Gd-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(2)(MeOH)(1), [Ho-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](2), [Er-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(H2O)(3), [Yb-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(4) [DEA = Diethanolamine] cores. The impetus for this study was to explore the magnetic behaviour of lanthanide ions which are often ignored or overlooked. X-ray crystal analysis show that these complexes are isostructural and exhibit an interesting butterfly like topology. The semi-rigidity and asymmetric nature of the ligand led to different coordination environment around the metal centres. The lanthanide ions adopt two types of geometry, a bicapped trigonal prism and a distorted square antiprismatic geometry around the metal center. Such dissimilar coordination environments around the lanthanide centre can have profound effects on their magnetic behaviour. Indeed, the magnetic measurements revealed significant magnetocaloric effect for octanuclear gadolinium complex 1 with magnetic entropy change (-Delta S-m ) of 31.4 J kg(-1) K-1 for Delta H = 9 T at T = 3 K whereas Er analogue complex 3 displayed SMM behavior.

Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.

Physical mechanism behind enhanced photoelectrochemical and photocatalytic properties of superhydrophilic assemblies of 3D-TiO2 microspheres with arrays of oriented, single-crystalline TiO2 nanowires as building blocks deposited on fluorine-doped tin oxid - Sadhu, Subha; Gupta, Preeti; Poddar, Pankaj (ACS Applied Materials & Interfaces, 2017)
In comparison to the one-dimensional (1D) semiconductor nanostructures, the hierarchical, three-dimensional (3D) microstructures, composed of the arrays of 1D nanostructures as building blocks, show quite unique physicochemical properties due to efficient photon capture and enhanced surface to volume ratio, which aid in advancing the performance of various optoelectronic devices. In this contribution, we report the fabrication of surfactant-free, radially assembled, 3D titania (rutile-phase) microsphere arrays (3D-TMSAs) composed of bundles of single-crystalline titania nanowires (NWs) directly on fluorine-doped conducting oxide (FTO) substrates with tunable architecture. The effects of growth parameters on the morphology of the 3D-TMSAs have been studied thoroughly. The 3D-TMSAs grown on the FTO-substrate showed superior photon-harvesting owing to the increase in light-scattering. The photocatalytic and photon to electron conversion efficiency of dye sensitized solar cells (DSSC), where the optimized 3D-TMSAs were used as an anode, showed around 44% increase in the photoconversion efficiency compared to that of Degussa P-25 as a result of the synergistic effect of higher surface area and enhanced photon scattering probability. The TMSA film showed superhydrophilicity without any prior UV irradiation. In addition, the presence of bundles of almost parallel NWs led to the formation of arrays of microcapacitors, which showed stable dielectric performance. The fabrication of single-crystalline, oriented, self-assembled TMSAs with bundles of titania nanowires as their building blocks deposited on transparent conducting oxide (TCO) substrates has vast potential in the area of photoelectrochemical research.

Polycrystalline MnGe2 thin films on InAs(001) substrates - Gutierrez-Naranjo, David; Holguin-Momaca, Jose T.; Solis-Canto, Oscar O.; Gupta, Preeti; Poddar, Pankaj; Espinosa Magana, Francisco; Olive-Mendez, Sion F. (Thin Solid Films, 2018)
We report on the growth of MnGe2 thin films on InAs(001) substrates using radio frequency-magnetron cosputtering. Polycrystalline thin films were obtained at a substrate temperature of 353 K. X-ray diffractometry was used to identify the tetragonal MnGe2 phase (space group 14/mcm). Measurements of the magnetic field and temperature dependence of the magnetization revealed that the MnGe2 thin films are ferromagnetic with a magnetization of 280 kAm(-1) and a Curie temperature of 62 K. Additionally, an antiferromagnetic component is observed at low temperatures, which may arise atomic disorder at the grain boundaries between MnGe2 crystallites.

Retention of anticancer activity of curcumin after conjugation with fluorescent gold quantum clusters: an in vitro and in vivo xenograft study - Khandelwal, Puneet; Alam, Aftab; Choksi, Arpankumar; Chattopadhyay, Samit; Poddar, Pankaj (ACS Omega, 2018)
Gold nanoparticles (Au NPs) have been thoroughly investigated for anti-cancer therapy. However, their undesired high gold content remains a problem when injected into the body for drug delivery applications. In this report, we made an effort to conjugate the curcumin molecules on the surface of gold quantum clusters (Au QCs) by a novel in situ synthesis method which provides an alternative route to not only reduce the metallic content but also increase the water solubility of curcumin and the loading efficiency. Here, curcumin itself acts as a reducing and capping agent for the synthesis of Au QCs. The UV−vis absorption, fluorescence, transmission electron microscopy, and electrospray ionization mass spectrometry results confirmed the synthesis of fluorescent Au QCs. Curcumin-conjugated Au NPs (C-Au NPs) and glutathione (GSH)-conjugated Au QCs (GSH-Au QCs) were also synthesized to visualize the effect of particle size and the capping agent, respectively, on the cytotoxicity to normal and cancer cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that the curcumin-conjugated Au QCs (C-Au QCs) were less cytotoxic to normal cells while almost the same cytotoxic to cancer cells in comparison to curcumin itself, which indicates that curcumin preserves its anticancer property even after binding to the Au QCs. However, C-Au NPs and GSH-Au QCs did not show any cytotoxicity against the normal and cancer cells at the concentration used. The western blot assay indicated that C-Au QCs promote apoptosis in cancer cells. Further, the in vivo study on severe combined immunodeficiency mice showed that C-Au QCs also inhibited the tumor growth efficiently without showing significant toxicity to internal organs.

Advances in the experimental and theoretical understandings of antibiotic conjugated gold nanoparticles for antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Poddar, Pankaj (ChemistrySelect, 2019)
The worldwide bacterial resistance to a wide range of antibiotics originates a global health concern and calls for the development of new antibacterial agents. Over the recent years, nanomaterials-based agents have been proven to be useful for the effective antibacterial applications. Notably, the gold nanoparticles (AuNPs) draw particular attention due to their biological inertness and easy surface functionalization. It is now established that the antibiotic functionalization on the AuNPs surfaces increases the antibacterial efficacy even towards the antibiotic-resistant bacterial cells. Moreover, the antibacterial efficacy can be further enhanced by photothermal therapy using antibiotic conjugated AuNPs. In this review article, we have reviewed the advances in the development of the synthesis methods of antibiotic conjugated AuNPs and gold nanoclusters, and their antibacterial efficacy. We have also discussed the developments in the theoretical understandings behind the interaction of antibiotic molecules with gold surface and its relation to the antibacterial activity. We believe that few parameters including the selection of antibiotic molecules, the method of its attachment to AuNPs, the purification of antibiotic conjugated AuNPs, and the quantification of conjugated antibiotic are crucial and needs to be properly addressed. Moreover, there are many other future directions discussed, for using antibiotic conjugated AuNPs more effectively for antibacterial therapy.
Keywords: Antibacterial; antibiotic; DFT calculations; gold nanocluster; Gold nanoparticle; multi-drug resistance; photo-thermal therapy

Downconversion luminescence-based nanosensor for label-free detection of explosives - Malik, Monika; Padhye, Preeti; Poddar, Pankaj (Acs Omega, 2019)
We report a selective and sensitive nanosensor probe based on polyethylenimine (PEI)-capped downconverting nanophosphors beta-NaYF4:Gd3+, Tb3+@PEI for the detection of 2,4,6-trinitrotoluene (TNT), both in water and buffer media. These downconverting phosphors were synthesized via a hydrothermal route and are known to show excellent chemical, thermal, and photostability. They emit sharp emission peaks centered at similar to 488, 544, 584, and 619 nm, among which the peak at similar to 544 nm was remarkably quenched (similar to 90%) by the addition of TNT without giving any new emission peak. The sensing mechanism is based on the formation of a Meisenheimer complex between the electron-rich amine-functionalized beta-NaYF4:Gd3+, Tb3+ nanophosphors and electron-deficient TNT molecule, which was prominently visualized by the change in the color of the solution from whitish to brownish yellow, enabling visual detection, followed by luminescence resonance energy transfer between the nanophosphors and the complex. A linear range for TNT detection was obtained from 0.1 to 300 mu M with a limit of detection as low as 119.9 nM. This method displayed excellent selectivity toward TNT over other nitroaromatic compounds, which had no influence on the detection. Moreover, various other classes of analytes, viz., amino acids, pesticides, and sugars, did not quench the luminescence intensity of the nanophosphors. This developed nanosensor probe possesses high, stable fluorescence brightness and capability for the selective and sensitive on-site recognition of TNT molecules in aqueous media, avoiding complicated strategies and instruments. Thus, this work promises to pave ways to many applications in the detection of ultratrace analytes.

Study of interfacial adhesion between nickel-titanium shape memory alloy and a polymer matrix by laser surface pattern - Samal, Sneha; Tyc, Ondrej; Heller, Ludek; Sittner, Petr; Malik, Monika; Poddar, Pankaj; Catauro, Michelina; Blanco, Ignazio (Applied Sciences-Basel, 2020)
The aim of this article is to investigate the interfacial adhesion of Ni-Ti shape memory alloy with a polymer matrix of Poly (methyl methacrylate) (PMMA). The surface pattern on Ni-Ti plates was channeled by a solid state laser machine. The laser machine allows for creating channels on the Ni-Ti surface for infiltration of the PMMA matrix, which could be attached as an intra-surface locking pattern to the Ni-Ti surface. The influence of the PMMA matrix on the surface of the NiTi plate was evaluated by thermomechanical analysis (TMA) and dynamic mechanical analysis (DMA). The surface characterization was carried out by an optical microscope on the PMMA/NiTi composite after mechanical testing. During mechanical testing, the polymer displays the multiple cracks in the longitudinal direction that result in slipping and fracture. TMA and DMA analyses were performed on the Ni-Ti- and PMMA-coated Ni-Ti ribbon to observe elasticity and the storage modulus for both samples. Better adhesion than 80 % was observed in the Ni-Ti surface, in the laser surface pattern, in comparison to the free plain surface. However, the polymer acts as mechanical backing that caused a reduction in the shape-memory properties of the composite material.
Keywords: adhesion; mechanical properties; NiTi composites; NiTi plate; PMMA; Polymer; surface features

Study of the phase-evolution mechanism of an Fe-Se system at the nanoscale: optimization of synthesis conditions for the isolation of pure phases and their controlled growth - Ghalawat, Monika; Poddar, Pankaj (Langmuir, 2020)
The iron selenide (Fe-Se) family of nanoparticles (FexSey-where x/y ranges from 1:2 to 1:1) has been fabricated by a thermal decomposition method. The control over solution chemistry has been developed by intensively investigating the effect of reaction parameters by means of wide-angle X-ray scattering, leading to the rich insights into the phase-evolution mechanism of the Fe-Se system. The phase transformation followed the FeSe2 -> Fe3Se4 -> Fe7Se8 -> FeSe sequence in the temperature range of 110-300 degrees C. The deep mechanistic insight helped in the identification of optimized conditions needed to crystallize the individual phase of the Fe-Se system as well as control of the morphology, crystalline phase purity, and thermal stability of the obtained Fe-Se nanoparticles.

Raman spectroscopy-based sensitive, fast and reversible vapour phase detection of explosives adsorbed on metal-organic frameworks UiO-67 - Sen Bishwas, Mousumi; Malik, Monika; Poddar, Pankaj (New Journal of Chemistry, 2021)
In this work, we report highly sensitive, selective, rapid, and reversible detection of explosive molecules in the vapour phase, adsorbed on metal-organic frameworks (MOFs) under ambient laboratory conditions. The sensing is based on the quenching of the Raman intensity of a zirconium-based MOF, Zr6O4(OH)(4)(dcppy)(6) (MOF 1, UiO-67-dcppy; dcppy is 2-phenylpyridine-5,4'-dicarboxylate), where 50% of the signal quenches swiftly within similar to 5 s of its exposure to trinitrophenol (TNP) vapours, while 90% of the Raman signal was quenched in 30 s. The high surface area of porous MOFs provides increased adsorption of various nitro analytes. The quenching of Raman peaks resulted from the pi-pi interactions of the analytes with the benzene ring of the MOF. The sensors have also been proven to be reversible and stable by mild heat treatment (80 degrees C for 5 min). These notable results using Raman spectroscopy point to a new and important approach towards explosive sensing using metal-organic frameworks considering their vast versatility. This work emphasizes the importance of a non-invasive and non-destructive technique that can be used to develop handheld vapour phase explosive detectors.

Study of growth kinetics of Fe3Se4 nanocrystallites and the influence of size and shape tunability on their magnetic properties - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2021)
Crystalline iron selenide (Fe3Se4) nanoparticles (NPs) present a useful model system for a fundamental understanding of magnetism apart from having potential applications in permanent-magnet-related technologies. Despite significant advancements in understanding of the nucleation and growth processes, control over size and shape tunability is nontrivial, especially for the transition metal chalcogenides (TMC). The Wulff theorem states that if a crystal can grow purely under thermodynamic control of parameters then it will adopt the shape determined by the surface-energy minimization, i.e., the surface energy minimization will drive the growth of each crystalline facet. However, the known or unknown, controllable or uncontrollable parameters of a typical reaction which makes kinetic growth more art than science, depending upon whether we understand them or not. There is hardly any study based on existing models and theories to explain the TMC morphology evolution. In this work, there is a conscious effort to know, understand, and control the individual role of various reaction pathways on the shape and size of the Fe3Se4 nanocrystals. A qualitative growth mechanism is proposed based on the diffusion and reaction processes. Furthermore, the influence of shape/size on the magnetic parameters such as coercivity (H-C), magnetization (M-60kOe), effective magnetic anisotropy constant (K-eff), energy product (BHmax), and average blocking temperature (T-B) is investigated for Fe3Se4 NPs. After diving deeper into the science of crystal growth, our insight provides valuable guidance on experimental conditions for the synthesis of Fe3Se4 NPs with tunable sizes/shapes which for the first time can be extended to most TMCs.

Formation of zircon-type DyCrO4 and its magnetic properties - Ughade, Supriya; Joshi, Bhavana; Poddar, Pankaj (Ceramics International, 2022)
The formation mechanism of hydrolytic sol-gel synthesized DyCrO4 with a complexing agent in acidic and basic mediums is thoroughly studied. The role of complexing agents and pH on phase formation temperature is also intensively investigated. The formation temperature for DyCrO4 is similar to 500 degrees C in the absence and presence of complexing agents such as oxalic acid and ethylenediaminetetraacetic acid (EDTA) at pH 10. When critic acid is used, the DyCrO4 forms with Cr2O3 impurity. The crystallite size in the presence of a complexing agent in the basic medium is similar to 55 nm which is small as compared to only ammonia solution. The various reaction modes lead to tetragonal zircon-type DyCrO4 at similar to 500 degrees C, transforming into orthorhombic perovskite DyCrO3 at 800 degrees C. The magnetization curve shows the ferromagnetic behavior of DyCrO4 below transition temperature T-c similar to 21 K. This low T-c makes nanocrystalline DyCrO4 a potential material for cryogenic applications.
Keywords: Complexing agent; DyCrO4; Formation mechanism; Hydrolytic sol-gel method; pH

Luminescence turn-off detection of metal ions and explosives using graphene quantum dots - Jyotsna, Shubhra; Sadhu, Subha; Sharma, Vinay; Gupta, Preeti; Sharma, Geeta; Poddar, Pankaj (MRS Communications, 2022)
Green luminescent graphene quantum dots (GQDs) obtained from combustion of white printing paper were used for detection of fourteen different metal ions and six different explosives in an aqueous medium. These were obtained using a microwave-assisted synthesis process. After optimizing the experimental conditions (pH 6; quantum yield (QY) similar to 38.2%), a sensitive sensing system was developed to detect explosives and free residual metal ions in the environment based on fluorescence quenching of GQDs. The as-synthesized GQDs, as a sensing system, is most sensitive for Cu2+ ion and 2,4-DNP with a detection limit of 0.62 mu M and 0.50 mu M, respectively.

Remarkable effect of Fe and Se composition on magnetic properties-comparative study of the Fe-Se system at the nanoscale - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2022)
Herein, for the first time, the correlation between the phase structure and the magnetic properties of the Fe-Se system has been presented for FexSey compounds-where x/y ranges from 1:2 to 1:1. These phases-orthorhombic (FeSe2), monoclinic (Fe3Se4), hexagonal (Fe7Se8), and tetragonal (beta-FeSe)-were synthesized using a one-pot thermal decomposition route at the nanoscale. The magnetic properties vary enormously with change in the Fe/Se ratio due to the change in the Fe2+/Fe3+ ratio, crystal field environment around the Fe ions, magnetocrystalline anisotropy, Fe vacancies, and so forth. Among the four Fe-Se phases studied, two of them, Fe3Se4 and Fe7Se8, are ferrimagnetic below similar to 300 K and show semihard magnetic properties. The other two phases FeSe2 and beta-FeSe exhibiting weaker magnetism are less known for their magnetic properties. All these phases are prone to surface oxidation despite surface passivation, and its effect on the magnetic moment will be pronounced for the phases with weak magnetization such as FeSe2 and beta-FeSe.

Ferroelectric polarization and iron substitution synergistically boost electrocatalytic oxygen evolution reaction in bismuth oxychloride nanosheets - Singh, Dinesh; Joshi, Bhavana; Poddar, Pankaj (Langmuir, 2023)
Ferroelectric materials have gained significant interestin variouskinds of water splitting, but the study of ferroelectric materialsfor electrocatalytic water splitting is in its infancy. Ferroelectricmaterials have spontaneous polarization below their Curie temperaturedue to dipolar alignment, which results in surface charges. In 2Dferroelectric materials, spontaneous polarization depends on thickness.Herein, we report that thickness-dependent ferroelectric polarizationin 2D nanosheets can also accelerate the oxygen evolution reaction(OER) along with the tailored active surface area of exposed crystallinefacets, which improves the electrocatalytic activity relatively. Iron-substitutedBiOCl nanosheets of varying thickness are fabricated by varying thepH using a facile coprecipitation method. The substituted iron enhancespolarization and electrochemical active sites on the surface. Thefindings in this study show that the exposed (001) facet and higherthickness of the nanosheets have high ferroelectric polarization and,in turn, superior electrocatalytic activity and remarkable stability,requiring low overpotentials (348 mV and 270 mV at 100 mA/cm(2) and 10 mA/cm(2)) in alkaline (1.0 M KOH) electrolyte. Asthe thickness of the nanosheets is decreased from 140 to 34 nm, theelectrocatalytic performance of iron-substituted BiOCl nanosheetsstarts to reduce due to the lower Coulomb-Coulomb interactionand the increasing depolarization.

Investigating the ferrimagnetic behaviour of trigonal 3C Fe7S8 nanoparticles - Jyotsna, Shubhra; Poddar, Pankaj (Bulletin of Materials Science, 2023)
The magnetic properties of trigonal 3C Fe7S8 nanoparticles, synthesized via the thermal decomposition method, are investigated using temperature-dependent zero-field cooled (ZFC) and field-cooled (FC) magnetization (M-T) curves. The M-T data, recorded at 100 and 1000 Oe, reveal magnetic ordering with high Curie transition temperature (T-C > 300 K) in the specimen. The magnetization vs. applied magnetic field (M-H) data measured in the temperature range from 7 to 300 K show that the compound exhibits ferrimagnetic ordering. The values of coercivity (H-C), saturation magnetization (M-60 kOe) and remanent magnetization (M-R) appear to increase at lower measuring temperatures. As the result of increasing M-60 kOe at lower measuring temperatures, within the temperature range of 7 to 300 K, the maximum energy product (BHmax) has the highest value of 128 kG Oe at 7 K.
Keywords: anisotropy; energy product; Fe7S8; ferrimagnetism; Pyrrhotites; trigonal phase

Scalable synthesis of dodecanethiol-capped bismuth nanoparticles by a solvent-free solid-state grinding method for reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (Langmuir, 2023)
Thiol-capped metal nanoparticles have two constituents:an inorganicmetal and an organic molecule as a shell. Both characters are inbuiltin the structure of the metal thiolate. Herein, we have investigatedbismuth dodecanethiolate as a precursor for the synthesis of dodecanethiol-cappedbismuth nanoparticles (Bi NPs) by a solid-state grinding method. Byusing sodium borohydride and bismuth dodecanethiolate, crystallinebismuth nanoparticles are synthesized in a solvent-free environmentat room temperature (24 & PLUSMN; 4 & DEG;C). Bi NPs are tested for catalyticactivity by reducing 4-nitrophenol (4-NP) to 4-aminophenol (4-AP)with an excess of NaBH4. Dodecanethiol-capped bismuth nanoparticlesexhibit an efficient reduction of 4-NP to 4-AP within 12 min. Additionally,these nanoparticles remain catalytically active for up to three cycles.

Self-powered wearable breath sensor cum nanogenerator using AuNR-rGO-PVDF nanocomposite - Bang, Amruta D.; Ghalawat, Monika; Poddar, Pankaj; Kulkarni, Sulabha K.; Adhyapak, Parag V. (IEEE Sensors Journal, 2023)
Breathing is the most important function of living being. It is well known that breath contains 90% humidity along with various gases and volatile organic compounds (VOCs). These gases are released during various metabolic activities in the body. These gases present in the breath can act as biomarkers to showcase healthiness or abnormalities in the body. Therefore, breath sensors are the need of time to detect diseases at early stages and in noninvasive way. Herein, we report, simple breath sensor using Au nanorods (AuNRs) and its nanocomposite with reduced graphene oxide (rGO) and polyvinylidene fluoride (PVDF). The nanocomposites system is designed in such a way that each component has its advantages for breath sensing. Here, AuNR being a good humidity sensitive material detects the breath efficiently. The ss phased PVDF being a very good ferroelectric material, contributes for voltage generation during sensing and enables the device to be self powered. The highly conducting rGO increases the sensitivity and voltage generation by facilitating the electron transport in the nanocomposite system. The nanocomposite was optimized with respect to PVDF, rGO and Au concentration. The as-synthesized materials were characterized by physiochemical characterization techniques such as field emission scanning electron microscopy (FESEM), X-ray diffraction analysis (XRD), UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The ss phase formation of the PVDF was confirmed from the XRD peak at 20.41 degrees. SEM results revealed that AuNR have length 15-20 nm and aspect ratio similar to 3-4. Breath sensing tests were carried out for as synthesized nanocomposite material. The nanocomposite exhibited high sensitivity towards breath and generated the voltage of similar to 0.7 V within 0.8 s.
Keywords: Au nanorods (AuNRs); breath analyzer; breath sensor; nanogenerator

Systematic study of rare-earth ions size-dependent structural phase transition from monazite to zircon-type in rare earth chromates using Raman spectroscopy - Ughade, Supriya; Poddar, Pankaj (Journal of Raman Spectroscopy, 2023)
Rare earth chromates (RCrO4) undergo monazite to zircon-type structural phase transition due to a decreased rare-earth ion size. They also exhibit an intermediate mixed phase. However, there is no systematic study on the influence of structural distortion on their phononic behavior, which is quite sensitive to subtle environmental variations. A change in the room temperature phononic spectrum was studied in the family of RCrO4 compounds, where R was varied from La to Yb using Raman modes. With an increase in the atomic number from Nd to Yb for zircon-type phases, the external translational and rotational modes were observed to shift towards lower and higher wavenumbers, respectively. At the same time, all internal vibrational modes shifted towards higher phonon energies. A comparison between Raman modes for monazite, intermediate, and zircon-type RCrO4 phases showed a gradual shift in the internal modes towards a higher wavenumber. The confirmation of the change in Raman modes with the decreasing radius was found by comparing the rare-earth elements in DyCrO4 and LaCrO4 with non-rare-earth elements in YCrO4.
Keywords: monazite-type; Raman spectroscopy; rare earth chromates (RCrO4); YCrO4; zircon type

In situ synthesis of metal (Bi0)-semiconductor [BiOX (X = Cl, Br, and I)] nanocomposites as a highly effective catalyst for the reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (New Journal of Chemistry, 2024)
The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) has been efficiently catalyzed by in situ generated Bi-0-BiOX (X = Cl, Br, I) nanocomposites in the presence of sodium borohydride (NaBH4). The hierarchical 3D arrays of precursors (BiOCl, BiOBr, and BiOI) have been synthesized by a facile co-precipitation method at ambient temperature. The metallic Bi-0 is generated in situ by partial reduction of the Bi3+ ions in BiOX (X = Cl, Br, and I) mediated by NaBH4 during the conversion of 4-NP to 4-AP. In situ generated Bi-0-BiOX shows better catalytic activity than Bi-0-BiOX composite formed by mixing individually synthesized metallic Bi-0 particles with semiconducting BiOX nanoparticles. The Bi-0-BiOI nanocomposite demonstrated higher catalytic activity (k(app) = 0.529 min(-1)) compared to Bi-0-BiOCl (k(app) = 0.095 min(-1)) and Bi-0-BiOBr (k(app) = 0.098 min(-1)) due to its efficient conversion into metallic Bi-0. The approximate percentage composition of in situ generated metallic Bi-0 on the surface of BiOCl, BiOBr, and BiOI is nearly 10, 17, and 25%, respectively. Further, the reduction of 4-NP has been completed within 24, 22, and 6 minutes by in situ generated Bi-0-BiOCl, Bi-0-BiOBr, and Bi-0-BiOI nanocomposites from BiOCl, BiOBr, and BiOI, respectively. Extensive studies have been conducted to generate a better understanding of the actual catalytic sites present on the surface of the catalysts.

Poly(N-vinylpyrrolidone)-assisted crystal growth of zeolitic imidazolate framework (ZIF-67) and electrochemical properties of its derivatives for flexible supercapacitors - Jain, Manisha; Joshi, Bhavana; Poddar, Pankaj (Crystal Growth and Design, 2024)
A simple and explicit wet chemical method enables the room-temperature crystallization of the zeolitic imidazolate framework (ZIF-67) using cotton-cloth (CC) as a substrate; where time-dependent Avrami's kinetic studies demonstrated sluggish nucleation and fast crystal growth resulting in unprecedented morphologies-truncated cubes [synthesized without poly(N-vinylpyrrolidone); PVP], and rhombic dodecahedra (with PVP) with average sizes ranging from 500 nm to 1.41 mu m; wherein amphiphilic PVP plays a crucial function of structure directing agent by modulation of complex formation and deprotonation equilibria. To study the potential of pristine ZIF-67 (ZP0) and PVP-functionalized ZIF-67 (ZP50, ZP100, and ZP200) grown on the CC substrate for application as a flexible electrode in supercapacitors, ZP0, ZP50, ZP100, and ZP200 were annealed to form CZP0, CZP50, and CZP100, respectively. Areal capacitances of 181 and 214 mFcm(-2) were achieved at a current density of 1 mAcm(-2) and a potential window of 1.6 V for CZP0 and CZP100, respectively, and compared to the derivatives without PVP; CZP100 exhibited a superior energy density of 76.3 mu Whcm(-2) and a capacitance retention of 84.3% after 5000 cycles at a current density of 0.5 mAcm(-2).

An in-depth study of the Fe-Se system at the nanoscale reveals remarkable results on the electrocatalytic oxygen evolution reaction - Singh, Dinesh; Ghalawat, Monika; Poddar, Pankaj (European Journal of Inorganic Chemistry, 2025)
A catalyst for an electrocatalytic oxygen evolution reaction (OER) is a key component of the large-scale storage of renewable energy through the conversion of water into oxygen and hydrogen. Iron-based selenide materials are currently being considered as potential options for electrocatalytic oxygen evolution reaction (OER) because of their, widespread availability, low cost, and outstanding performance. In this study, we employed a thermal decomposition method to synthesize all stable phases of the Fe-Se system, including Fe7Se8, Fe3Se4, FeSe2, and FeSe. Additionally, we slurry-coated these phases onto a three-dimensional (3D) nickel foam substrate. The prepared 3D electrodes of Fe7Se8, Fe3Se4, FeSe2, and FeSe exhibit remarkably low overpotentials of 270, 276, 299, and 289 mV at a current density of 50 mA/cm2 for OER. In addition, the catalytic activity for OER is also tested on glassy carbon electrodes to compare its performance with the Ni-foam 3D substrate. The Fe7Se8 phase in the Fe-Se system exhibits the highest catalytic activity towards OER on both substrates due to variations in the Fe2+/Fe3+ ratio and the presence of Fe vacancies (cation vacancies) within the crystal lattice. Moreover, a faradaic efficiency of 98 % was exhibited by Fe7Se8 for the oxygen evolution reaction (OER).
Keywords: Iron selenide system; OER electrocatalyst; Thermal decomposition method

Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite

Hierarchical 3D Fe-doped Bi2MoO6 arrays supported on a Ni foam: an effective electrocatalyst for alkaline water splitting - Singh, Dinesh; Poddar, Pankaj (Nanoscale, 2026)
Electrocatalytic water splitting is a viable route to sustainable hydrogen generation; however, designing high-performance, stable catalysts remains a considerable challenge. Bismuth-based materials have not yet been well studied for electrocatalytic alkaline water splitting, despite their favourable electronic structure and chemical stability. Here, iron-doped hierarchical three-dimensional (3D) Bi2MoO6 arrays have been grown in situ on a 3D conductive nickel foam (NF) substrate using a facile solvothermal method. The optimal Fe-doped Bi2MoO6/NF (Fe, 5 mol% substituting Bi) or BMOF-5 electrocatalyst exhibits excellent electrocatalytic activity towards the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline media (pH similar to 14.0) owing to abundant active sites in the hierarchical 3D framework, high electrical conductivity, and superhydrophilic nature. At a current density of 10 mA cm-2, the BMOF-5 electrocatalyst requires 262 mV and 153 mV overpotentials for the OER and HER, respectively. In addition, a potential of 1.62 V is required by the BMOF-5/NF parallel to BMOF-5/NF cell at a current density of 10 mA cm-2 for overall water splitting. The BMOF-5/NF electrocatalyst shows durability of 24 h and 22 h for the HER and OER in a 1 M KOH electrolyte at current densities of 100 and 10 mA cm-2, respectively. In this study, a small amount of iron plays an important role in altering the electronic environment of Bi2MoO6, increasing the electrochemically active sites and reducing the charge-transfer resistance at the electrode-electrolyte interface. In addition, this work presents an easy and efficient approach to enhance the electrocatalytic performance of Bi2MoO6, which is of significant practical importance.

Tuning the electric dipole transitions (5D0 → 7F2 and 5D0 → 7F4) in thin Eu-doped BiOCl nanosheets - Singh, Dinesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2026)
The polarization and depolarization of layered ferroelectric materials can be tuned by altering the thickness of nanosheets, apart from controlling inter/intralayer distances, doping of ions, the surrounding dielectric environment, etc. In two-dimensional, single-crystalline ferroelectric nanosheets, the reduction in the thickness facilitates the internal electric field (IEF), which leads to enhanced depolarization. BiOCl is a layered ferroelectric material with repeating layers of [Bi2O2](2+), which exhibit anisotropy. However, the depolarization and polarization of BiOCl are significantly influenced by the thicknesses of its nanosheets. Herein, 1-dodecanethiol-capped europium (Eu3+)-doped BiOCl thin nanosheets resembling a two-dimensional structure have been synthesized using the solid-state grinding method at ambient temperature. As a result of the depolarization effect, the strength of the electric dipole transitions D-5(0) -> F-7(2) and D-5(0) -> F-7(4) increases in the Eu-doped BiOCl nanosheets. However, thiol capping helps in synthesizing uniform 2D nanosheets with reduced vertical dimensions (thickness near 15-30 nm). It is observed that all of the prepared samples with varying Eu ion concentrations show uniform nanosheet-like morphology, as confirmed by electron microscopy (FESEM and HRTEM). As the concentration of Eu ions increases in the BiOCl host lattice, the intensity of electric dipole transitions also increases (until 9 mol %). Fourier transform infrared spectroscopy (FT-IR) reveals the coating of 1-dodecanthiol on the Eu-doped BiOCl molecule. Furthermore, the Eu-doped BiOCl samples showed prominent far-red emission at 700 nm, corresponding to the D-5(0) -> F-7(4) transition. Moreover, this work emphasizes the synthesis of Eu-doped phosphor at an ambient temperature of 24 +/- 2 degrees C and generates a deeper understanding of the abnormal electric dipole (D-5(0) -> F-7(4)) transition.